GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 570331814 species occurrences available in GBIF matching the query: All data. The dataset includes 570331814 records from 13237 constituent datasets: 118309 records from Therevid PEET Project. 477 records from Biodamaz1. 98 records from Rund ums Cani. 15 records from Taxonomy of European Damaeidae (Acari: Oribatida) I. Kunstidamaeus Miko, 2006, with comments on Damaeus sensu lato. 511 records from Coleoptera of Swierklaniec Forest. 1722 records from Cambridgeshire & Peterborough Biological Records Centre - Orthoptera dataset held by CPERC. 45 records from Scottish Natural Heritage - Surveys of Najas flexilis (Slender naiad) in Scotland 2004 â 2011. 583 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-847B. 1252 records from Aquatic Coleoptera Conservation Trust - SNH site condition monitoring of SSSIs for water beetles 2010. 7410 records from Helgeland Museum, Lepidoptera. 91 records from Birdrace-Enger_am_Spektiv-Herford. 49 records from Schulgartengelände des Hans-Carossa-Gymnasiums (Berlin). 169 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 299 records from Total foraminifera counts of multinet M21/3_MSN662. 2 records from (Fig. 5) Pollen analysis of the Furo do Chato core. 11 records from Microzooplankton abundance and biomass at station TT043_17-1. 6 records from Wiese. 15 records from Diatom abundance measured on water bottle samples at station PS58/090-4. 255 records from Planktic foraminifera counts of sediment core RC09-150. 22 records from Geophagus abalios, G. dicrozoster and G. winemilleri (Perciformes: Cichlidae), three new species from Venezuela.. 1470 records from (Table 10) Distribution of planktonic foraminifers in ODP Hole 108-662A. 16604 records from Iberian Odonata distribution: data of the BOS Arthropod Collection (Univ. Oviedo, Spain). 6 records from Rango, comportamiento, tamaño de población y conservación de felinos en el Volcán de Colima. 109504 records from Plant Specimens of Kurashiki Museum of Natural History. 1684 records from MfN Fish Collection, Zoology. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station MAY-1995-D4. 123 records from Range table from planktonic foraminifers in ODP Hole 180-1111A. 48 records from Range table from planktonic foraminifers in ODP Hole 180-1116A. 1460 records from Range table from benthic foraminifers in ODP Hole 151-909C. 61 records from A taxonomic revision of the catshark genus Holohalaelurus Fowler 1934 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae), with descriptions of two new species.. 418 records from Type Collection of the Seto Marine Biological Laboratory, Kyoto University. 86 records from Besonderer Ort - besondere Natur: Die Mainzer Zitadelle. 78 records from Birdrace-Die_Laufenten-Braunschweig. 15 records from Kirchheller Heide ( Bottrop). 1023 records from (Appendix Table 1) Number of planktonic foraminiferal genera and species in Late Creatceous sediments of ODP Hole 122-762C from the Exmouth Plateau, eastern Indian Ocean. 126 records from Total foraminifera counts of multinet M11/1_MSN517. 11 records from Microzooplankton abundance and biomass at station TT045_4-1. 4 records from Microzooplankton abundance and biomass at station TT050_26-17. 6 records from Microzooplankton abundance and biomass at station NBP97-08-37-4. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-10-2. 26 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/357-1. 116 records from Phytoplankton abundance and species composition in the Sicily Channel in October 1991. 182 records from Biotope entdecken im Kockmecker Siepen (Sauerland). 6 records from Nannofossil abundance of Hole 67-494A. 13 records from Diatom abundance measured on water bottle samples at station PS58/042-2. 20 records from Distribution of planktonic foraminifera and other biogenic components in ODP Hole 113-693A (Figure 2). 3045 records from Obtención de la riqueza de aves y selección de especies susceptibles de monitoreo en la zona noroeste en el estado de Chiapas. 2427 records from Ibaraki Nature Museum, Mollusk collection. 578 records from (Table 3) Relative abundances of selected planktonic foraminifera of ODP Site 117-722. 321 records from Nova Scotia Department of Natural Resources, Subenacadie, NS, Canada. 368 records from Great Lakes Forestry Centre Insect Collection. 46156 records from Zooplankton in the bay of Biscay (1995-2004 Yearly spring DEPM surveys). 13 records from FND "Weißer Berg" Leißling. 20 records from The interstitial subsoil fauna of the medium beach level at Sarso Beach, Red Sea (Table 3). 62 records from Abundance of coccosphere-units of sediment core GIK23400-3. 31 records from Aktionstag Wiese am Vogelhammerkopf. 3709 records from Plant (MNHM-PL). 702 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 871 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 565 records from Biodiversidad de productores primarios de lagunas costeras del norte de Yucatán, México_2. 811 records from U. S. National Parasite Collection's holdings from Robert L. Rausch. 52181 records from ANTARCTIC PLANT DATABASE. 41548 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1985) (AfrOBIS). 36254 records from Fish collection of National Museum of Nature and Science. 127133 records from Fish specimens. 19164 records from The Gordon Alexander Orthoptera Collection. 1358 records from Electron Micrograph Database (Australian Antarctic Data Centre). 399 records from Colecciones Zoológicas de la Universidad de León, Colección de Poliquetos. 1353 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC12-294. 354 records from Foraminifera distribution of sediment core KS310. 160757 records from Slovenian Fungal Database - Boletus informaticus. 85 records from Unterbrucker Weiher. 195 records from Altenburg bei Bamberg. 181 records from Occurrence of mammalia relicts at site Kemathenhöhle. 22 records from Occurrence of mammalia relicts at site Castlepook Cave. 808 records from Range table from planktonic foraminifers in ODP Hole 154-925B. 27 records from Benthic foraminifera and algae abundance of Hole 81-553. 631 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 149-898A. 637398 records from Données ONF Faune-Flore-FOnge. 3 records from Analyses of the recent components of sediment core PS1215-2. 43 records from Vogelstimmenführung durch den Tiergarten. 196 records from Unser kleines Rasenstück/ Dürer-Gymnasium Nürnberg. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station AUGUST-1994-D4. 19 records from Occurrence of mammalia relicts at site Gröbern. 4 records from Occurrence of mammalia relicts at site Ahlen. 68 records from Occurrence of mammalia relicts at site l´Abri du Morin. 17 records from Benthic foraminifera abundance of Hole 11-108. 394 records from Range table from benthic foraminifers in ODP Hole 144-871C. 290333 records from AMNH Mammal Collections. 45 records from Pseudecheneis maurus, a new species of glyptosternine catfish (Teleostei: Sisoridae) from Central Vietnam.. 172 records from Redescription of Gymnotus coropinae (Gymnotiformes, Gymnotidae), an often misidentified species of Neotropical electric fish, with notes on natural history and electric signals.. 6943 records from DMNS Egg Collection (Arctos). 1180 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Water Vole Records. 6 records from Synodontis acanthoperca, a new species from the Ogooue River system, Gabon with comments on spiny ornamentation and sexual dimorphism in mochokid catfishes (Siluriformes: Mochokidae).. 398 records from Tsetse flies of East Africa update. 5570 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 1 records from Tunicata ZMK. 3762 records from Inventaire National du Patrimoine Naturel : Flore protégée du Dauphiné. 74 records from Birdrace_Gätkes_Schergen-Helgoland. 128 records from Total foraminifera counts of multinet M42/3_MSN1359. 136 records from Total foraminifera counts of multinet PO247/2_MSN1380. 13 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/061-3. 3 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_832-7. 1 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 122 records from Relative abundance of benthic foraminifera of sediment core GIK13292-3, East Atlantic off Senegal and Gambia (Table 3). 3324 records from Crustacea collection of the Finnish Museum of Natural History. 169 records from Whale log - observations from ANARE voyages. 1740 records from Monitoring data from the federal state Berlin (Germany). 156 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 176 records from (Appendix E) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 161-976C. 1264 records from Hare Survey of Ireland 06/07 - Non Hare records. 77152 records from Conchological Society of Great Britain & Ireland - Mollusc (marine) data for Great Britain and Ireland. 1 records from Hoplophora decumana. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 24469 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Anfibios. 79 records from Plasm bearing foraminifera counts of multinet M21/2_MSN628. 35 records from Planktic foraminifera of sediment core GeoB1404-3. 5 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_818-16. 16 records from Phytoplankton abundance at station Sechin_2003-12-03_1, Casma, Peru. 240 records from Coleoptera identified from the Woolwich Manor Way site, Becton, London. 40 records from Coccolith counts of multinet M32/5_MSN979. 2 records from Range table from nannofossils in ODP Hole 198-1207A. 4702 records from Amphibian specimens. 2 records from Akita Prefectural Museum＋Hagfishes Specimens of Akita Prefectural Museum. 317 records from Terrestrial Heteroptera Recording Scheme (Shieldbugs & allied species) - iSpot (2008-2010): Shieldbugs & allied species. 218 records from (Table 6) Benthic foraminiferal genera in DSDP Core 95-612-5. 1320 records from (Table 8D) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 15-4 through 19-3. 227 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 2546 records from The atlas of butterflies in Kraków. 4390 records from Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 13403 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 22978 records from Humber Environmental Data Centre - Humber Environmental Data Centre - Non Sensitive Records from all taxonomic groups. 17 records from Hazel Dormouse in Ireland. 2391 records from Ohio State University Tetrapod Division - Reptile Collection (OSUM). 3065 records from Colección de Ofidios Museo de La Salle Bogotá (MLS). 36 records from Salzwiese Diekskiel. 126 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, >125 µm fraction. 41 records from Abundance of living benthic foraminifera in sediment core CD86_07_BC4. 15 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_10-CTD124. 81 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 74-527. 45 records from (Table A.09) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (125-250 µm). 50 records from Leben in den Elbwiesen. 45 records from Nannofossil abundance of Hole 64-481A. 16 records from Nannofossil abundance of Hole 11-106B. 75 records from Planktic foraminifera counts of sediment core V26-124. 7208 records from Catálogo y base de datos preliminar de la flora de Sinaloa. 12 records from Distribution of meiobenthos in sediment core M19_239-2 of the northeastern Atlantic (Table 1). 18 records from Nannofossil abundance of Hole 8-73. 66 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 113-689. 394 records from (App 7) Relative contents of benthic foraminifera species in sediments accumulated during last 1000 years, Core ASV11-987. 7 records from Appendicularia abundance of station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 2). 19386 records from Base de datos de aves mexicanas del Natural History Museum, Tring, Inglaterra. 4540 records from Inventario de la mastofauna en las reservas de la biosfera Desierto del Vizcaíno y Valle de los Cirios. 62 records from Phytoplankton abundance during Akademik Vernadsky cruise AV22. 13960 records from Collection Trichoptera - SMF. 12836 records from Planktic foraminifera assemblage in sediment core MD97-2142. 66 records from (Appendix A5) Relative abundances of planktonic foraminifera of sediment core GeoB1711-5. 27 records from Herbarium Senckenbergianum (FR) - Protista. 1304 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-127. 495 records from (Table A.08) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (80-150 µm). 35 records from Occurrence of mammalia relicts at site Gura Cheii-Rasnov. 286 records from (Figure 2) Distribution chart of dinoflagellate cysts of Cretaceous age from ODP Hole 103-638C. 700 records from (Table 3c) Foraminiferal distribution chart of ODP Hole 122-762C. 7 records from Collection Malakologie - SMNG. 21172 records from Weddell Seal Sightings, Vestfold Hills, Antarctica. 6629 records from Benthic biodiversity along the central coast in the Brazilian EEZ (OBIS South America, BRAZIL) (OBIS South America, BRAZIL). 33883 records from Joint Nature Conservation Committee - Vegetation surveys of coastal shingle in Great Britain. 4380 records from RMT Trawl catch from the 1980/81 V5 FIBEX voyage (Australian Antarctic Data Centre). 427 records from Planktic foraminifera abundance of Hole 76-533A. 16344 records from Coleccion de sonidos ambientales. 621 records from Biological Records Centre - UK Ladybird Survey data from iRecord. 1 records from A new species of Asphinctopone (Hymenoptera: Formicidae: Ponerinae) from Tanzania.. 10271 records from Carabidae of Poland. 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 205653 records from Inventaire National du Patrimoine Naturel : Oiseaux nicheurs de France. 180 records from Assemblage of living benthic foraminifera in sediment core GeoB3701-1. 1278 records from (Appendix 2-6) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 58-445 in the western Pacific Ocean. 45 records from Collection Bryozoa - ZIM Hamburg. 2577 records from Avifauna de la Isla de Cozumel, Quintana Roo_3. 186 records from (3) Sea Surface Temperature (SST) reconstructed from the percentage of Neogloboquadrina pachyderma sinistral in sediment core MD02-2488 during the period 50-140 ka. 894 records from CNAN/Arañas sinantrópicas. 30 records from A new species of Farlowella Eigenmann and Eigenmann (Siluriformes: Loricariidae), a stickcatfish from Bolivia.. 69 records from (Table 3c) Distribution of planktonic foraminiferal tests in sediments from Core NKA-40T. 3524 records from Escarabajos y moscas de los bosques de niebla del sureste mexicano (Coleoptera: Scarabaeoidea; Diptera: Syrphidae y Calliphoridae). 3538 records from (Table 4) Paleocene to Eocene planktonic foraminifera of DSDP Hole 29-277. 18473 records from Australian Antarctic Division Herbarium. 802 records from Biological Collection, National Institute of Oceanography, Goa, India. 85 records from Schulgelände IGS Kaufungen. 83 records from Occurrence of mammalia relicts at site Spitzbubenhöhle. 691 records from Foraminifera abundance of Hole 24-236. 1035 records from Foraminifera abundance of Hole 24-237. 62371 records from MLZ Bird Collection (Arctos). 132 records from Range table from benthic foraminifers in ODP Hole 144-876A. 3201 records from Weevils of the Carpathians. 99 records from G.B. Pant Institute of Himalayan Environment & Development - Plants of West Himalaya, India. 10 records from A new Neoplatyura Malloch from Finland (Diptera, Keroplatidae). 7 records from Calvia explanata sp. n. (Coleoptera: Coccinellidae: Coccinellinae) from the Indian Subcontinent. 10234 records from Collection entomologique Barthélémy. 19 records from Goethe-Hauptschule/Projekt I-10. 25 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >125 µm. 149 records from Total foraminifera counts of multinet PO247/2_MSN1372. 27 records from Total foraminifera counts of trap L3_92_45. 1 records from Wirtschaftsgrünland, Intensiv genutze Wiese. 12 records from Nannofossil abundance of Hole 31-299. 14 records from Ostracoda abundance of Hole 44-392A. 5538 records from Colección Alberto Tinaut (Formicidae). 1660 records from Revisión de la subfamilia Asopinae (Hemiptera-Heteroptera-Pentatomidae) para México. 12 records from Microplankton abundance at bottle station SEPT-1999-K1. 1289 records from Percentages of planktonic foraminifera species in sediment core V22-222. 16 records from Occurrence of mammalia relicts at site Dorog. 376 records from Planktic foraminifera abundance of Hole 22-216. 1790 records from Planktic foraminifera abundance of Hole 9-77B. 130 records from Range table from planktonic foraminifers in ODP Hole 139-855C. 38 records from Dinoflagellate abundance of Hole 71-512. 10792 records from Fungi specimen detabase of Kanagawa Prefectural Museum of Natural History. 141 records from VFD-BW, Schönbuch: Pferdeweiden Breitenstein. 811 records from Amphibians and reptiles of Ireland. 781 records from RSPB - Bittern Annual Surveys in Britain 1990-2008 (SCARABBS). 1364 records from Irish Collembola records. 99 records from Streuobstwiese Stedar. 9 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, >150 µm. 14 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/090-2. 60 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/543-5. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_15-CTD175. 1045745 records from Herbarium of The New York Botanical Garden. 26 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Thinocoridae. 6746 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 2000 records from Shellfish (ASJK_MS). 4 records from Akita Prefectural Museum＋Specimens of Class Maxillopoda of Akita Prefectural Museum. 191859 records from herbario. 683018 records from The System-wide Information Network for Genetic Resources (SINGER). 48 records from Relative abundance of planktic foraminifera in sediment core K11. 60 records from (Table 7) Occurrence of selected diatom species in ODP Hole 119-744A. 96 records from Birdrace-federleser-Herford. 98 records from Planktic foraminifera abundance of Hole 74-528. 1845 records from (Table 8C) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 8-5 through 15-3. 69 records from Planktic foraminifera abundance of Hole 52-418. 3536 records from Live (Rose Bengal stained) benthic foraminifera of surface sediments of the Persian Gulf (Table 1). 534 records from Leopard Seal census, Heard Island 1987/88. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 1 records from Orthoptera - SMF. 221 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Turdidae. 320 records from Scottish Wildlife Trust - Ants: Formica Exsecta Records from Abernethy RSPB. 2728 records from Caracterización de la vegetación en los sectores de Aipe (Huila), Yaví (Tolima) y Dagua (Valle del Cauca), como insumo para la identificación de oportunidades de conservación y la recuperación de servicios ecosistémicos del bosque seco. 13325 records from Herbier du Bénin. 22224 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 209 records from (Appendix A) Palynofacies absoulte abundances of DSDP Hole 38-338. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 43 records from Gewässeruntersuchung Grötzinger Baggersee. 166 records from BIRDRACE Die Düsselmöwen. 106 records from BIRDRACE EFTAS-NLU Birdrace Team 2008. 66 records from Total living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >30 µm. 54 records from Plasm bearing foraminifera counts of multinet M21/2_MSN629. 74 records from Faunal assemblage of sediment core TR149-36. 8 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 464 records from Lepidoptera collection, NTNU, Trondheim. 268 records from Geometry of coccolith Coccolithus pelagicus in sediment core PS1113-1. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/553-3. 45 records from BIRDRACE Ohne Graureiher läuft nix!. 3139 records from (Appendix A) Agglutinated foraminifers in ODP Hole 123-765C. 1470 records from EDIT - ATBI in Spreewald (Germany). 60 records from (Table 5) Quality control of palynoclasts, palynomorphs and microplankton abundances in ODPHole 112-686B. 2025 records from Los crisomélidos del bosque mesófilo de la reserva de la biósfera El Cielo, Gómez Farías, Tamaulipas. 13427 records from CNPE/Coleccion Nacional de Peces. 6627 records from ATCC Fungi Collection Catalog. 1166 records from South Western Pacific Regional OBIS Data Bio Ross Subset (South Western Pac ific OBIS). 19 records from Antarctic Krill occurrence data from Japanese expeditions. 38 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB01 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 4 records from Occurrence of mammalia relicts at site Henauhof NW 2. 122 records from Occurrence of mammalia relicts at site Hunas. 2240 records from Derbyshire Biological Records Centre - Hemiptera Records 1969 - 2011. 2444 records from (Table 12A) Occurrences of planktonic foraminifers in selected samples of DSDP Holes 90-590 and 90-590A. 26079 records from Ohio State University Tetrapod Division - Bird Collection (OSUM). 893 records from (Table T1) Neogene dynoflagellate cyst occurrence in ODP Hole 186-1151A sediments. 994 records from Biological Records In Essex - Bat records for Essex from 1971 - present.. 35 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto11-19. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 4971 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF. 49406 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1985) (AfrOBIS). 4641 records from Lepidopterists Society Season Summaries 1973-1997. 836 records from Visual Plants (144.41.33.158) - Botanical garden, University of Hohenheim, Germany. 22367 records from Bird Collection. 1101 records from Relative abundance of ostracods in sediment core Co1202. 14 records from Radiolaria assemblage in sediment core GIK23259-2. 152 records from Planktic foraminifera abundance of Hole 16-159. 672 records from Range table from planktonic foraminifers in ODP Hole 155-938A. 216 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 1428 records from (Fig. 14) Distribution of dinoflagellate cysts in Early Cretaceous sediments of ODP Hole 103-638B in the North Atlantic. 55690 records from The First Atlas of Wintering Birds in Britain and Ireland: 1981/82-1983/84.. 104431 records from Field Museum of Natural History (Zoology) Fish Collection. 8162 records from CRI - Herbário Pe. Dr. Raulino Reitz. 1444609 records from Rotherham Biological Records Centre - Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 29 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5112-4. 85 records from Epifauna abundance in 2006-10 from an experiment in the Wadden Sea of List, Sylt. 2 records from Nannofossil abundance of Hole 6-50A. 79 records from Ostracoda abundance of Hole 34-319. 14 records from Benthic macrofauna abundance of sediment core 12930-081. 361 records from Water mite collection of Pauli Bagge. 40 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE272. 118 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2010. 122 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB07 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 337366 records from British Lichen Society - BLS Lichen Database: England. 1 records from Dinoflagellate abundance of Hole 19-183. 8540 records from Herbarium WRSL, Lichens Collection. 854 records from (Table T1) Abundance of stratigraphically important planktonic foraminifera in ODP Site 186-1150 sediments. 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 1594 records from Musée Vert ornithology collection. 61 records from Total foraminifera counts of multinet M10/2_MSN229. 46 records from Foraminifera species abundances from tow TT007_5-MOC9. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-20-5. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-081. 1000 records from Diplopoda (JJHA-DI). 268 records from (Table 5) Relative abundance of benthic foraminifera in ODP Hole 112-686A. 156 records from (Table 2) Distribution of some benthic foraminifera in ODP Hole 108-658A. 10203 records from Coleoptera specimen database of Osaka Museum of Natural History. 2418 records from Distribution of planktic foraminifera in sediment core GIK23415-9. 12 records from New data on the European species of three genera Scelionidae (Hymenoptera).. 10 records from Oberservation of birds at station PS14/157 along 49° West. 8008 records from Avistajes de espcies de valor especial en áreas protegidas del noreste de Argentina. 1 records from Nouvelles fourmis d'Afrique.. 1 records from On the Australian linyphiid spider Alaxchelicera ordinaria Butler, 1932 (Araneae). 18 records from A new species of Anabarhynchus (Diptera: Therevidae) from an ocean beach in south east Victoria. 205 records from Planktic foraminifera abundance of Hole 29-284A. 92 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-969A. 301 records from (Appendix 4, Table 4) Relative abundances of benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 12 records from (Table 3) Miocene biostratigraphy of the Hemmorian stage in Schleswig-Holstein. 2 records from Ireneopone gibber (Hym., Formicidae), a new genus and species of myrmicine ant from Mauritius.. 162150 records from Ditsong Museum. 144 records from Ehmkendorf. 46 records from Phytoplankton abundance at station DI183_11872#3. 3161 records from Census in Agrimey forest reserve (southern Benin). 881 records from (Table 2) Planktic foraminifera and their diversity indices of sediment surface samples from the Atlantic Ocean. 37 records from (Table 4) Carbon flux, paleoproductivity, relative abundance of foraminifera on sediment core PS2837-6. 13 records from Nannofossil abundance of Hole 11-103. 34 records from (Table 6B) Distribution of Mesozoic nannoliths at DSDP Hole 43-387. 215 records from (App 6) Relative contents of benthic foraminifera species in sediments from Core PS2718-6. 175 records from Range table from benthic foraminifers in ODP Hole 198-1207B. 2066 records from Range table from benthic foraminifers in ODP Hole 159-959D. 78 records from Microfossil abundance of Hole 21-206. 59928 records from Ifremer BIOCEAN database (Deep Sea Benthic Fauna). 371 records from Fossil occurrence of planktonic foraminifera from IODP Hole 315-C0001H. 65 records from Sternarchorhynchus curumim (Gymnotiformes: Apteronotidae), a new species of tube-snouted ghost electric knifefish from the lowland Amazon basin, Brazil.. 47 records from Occurrence of mammalia relicts at site Burgtonna. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 1390 records from Caracterización de avifauna de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 346 records from Benthic foraminifera counts of sediment core GIK23342-6. 62 records from Total foraminifera counts of multinet M21/4_MSN700. 83 records from Foraminifera species abundances from tow TT011_7-MOC66. 129 records from Dinoflagellate cysts from sediment core PS2458-4. 80 records from (Table 6) Distribution of the large, few-chambered Globigerinelloides species in the Lesches en Diois section. 279 records from (Table 3) Relative abundance of benthic foraminifera in ODP Hole 112-681A. 38 records from (Table 7) Pleistocene nannofossil range chart for ODP Hole 134-832A. 466734 records from ECNASAP - East Coast North America Strategic Assessment (OBIS Canada). 61010 records from Fish Collection of Hokkaido University. 28934 records from Coleção de Abelhas do Museu de Ciências e Tecnologia da PUCRS. 305 records from Flux data of NU2_trap (Table A1). 22 records from Sediment properties of core PLG95B_01BOXG. 1077 records from Percentages of planktonic foraminifera species in sediment core RC24-7. 167 records from Artenvielfalt auf den Elbwiesen (Dessau). 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 39 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200320. 5 records from Occurrence of mammalia relicts at site Prekonoska Pecina. 4 records from Occurrence of mammalia relicts at site Grotte Cotencher. 1973 records from Foraminifera abundance of Hole 61-462. 68 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-04. 207 records from Assemblage of living benthic foraminifera in sediment core GeoB3711-1. 144 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 11 records from Phytoplankton abundance at station Rigel_2_2005-03 in March 2005, Chipana, Chile. 4 records from "Am Riedert" im Westerzgebirge. 57 records from Royal penguin Eudyptes schlegeli census, Macquarie Island, 1984. 202 records from Dinoflagellate cysts from sediment core PS1295-4. 38 records from (Table 1) Chiasmolithus species and intermediate forms of ODP Holes 105-647A and 120-748B. 23146 records from BC Coastal Waterbird Survey. 3578 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, 2004-2009 â sensitive records. 123 records from Birdrace-SportfreundeTriller-Münster. 11 records from Occurrence of mammalia relicts at site l´Abri Caminade-Ouest. 2 records from Planktic foraminifera abundance of Hole 54-421. 229 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 457 records from Microbial Observatory of the Laboratoire Arago. 3182 records from Finnish Entomological Database: Heteroptera. 63 records from Plasm bearing foraminifera counts of multinet SO118_MSN1266. 124 records from Total foraminifera counts of multinet M10/2_MSN232. 31 records from Planktic foraminifera of sediment core GeoB1406-4. 7 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_230-23. 6 records from Microzooplankton abundance and biomass at station TT043_7-20. 821 records from Planktic foraminifera counts of sediment core V19-188. 103 records from Mammals (UWEP-MM). 23 records from Two new species of Pseudolaguvia (Teleostei: Erethistidae) from Bangladesh.. 1513 records from (Table 5) Ranges of benthic foraminifers from the late Oligocene to the early Miocene in ODP Hole 115-714A. 1399 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V22-182. 109 records from Dreilinden Gymnasium-Schulgelände. 297 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB01 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 114203 records from UTA Herpetology. 2737 records from Gunma Museum of Natural History, Molluscan Specimen. 4649 records from Inventaire National du Patrimoine Naturel : Flore de Sologne. 3 records from Res Ligusticae XXII. Diagnosi di nuove specie di miriapodi cavernicoli. 3 records from On two Italian Lithobius species described by Silvestri, with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda, Lithobiida). 1035 records from National Museum Of Marine Science & Technology. 114 records from Flora. 277 records from Naturschutzgebiet Börstig bei Hallstadt. 4 records from Sarcodine counts and carbon biomass at station TT008_5-PMOC5. 5037 records from Estudios bióticos: plantas, edafofauna epígea, anfibios y aves en los complejos de páramos los Nevados y Chilí-Barragán. 1677 records from Distribution of planktonic foraminifera in DSDP Hole 31-296 (Table III). 112 records from Werl macht sich auf die Suche. 19 records from Meiofauna abundance in sediment core 12930-036. 240 records from (Table 1) Distribution of planktonic foraminifers in ODP Hole 126-787B. 8470 records from (Table 12) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-714A. 80 records from Collection Copepoda - SMF. 11 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR50. 271 records from kisti_microb. 8 records from Planktic foraminifera abundance of Hole 94-611B. 279 records from Range table from planktonic foraminifers in ODP Hole 175-1077A. 163 records from Benthic foraminifera and nannofossil abundance of Hole 40-364. 139 records from Siliceous microfossil occurrence, Site 177-1093. 2 records from Abundance of benthos infauna at station GIK23024-1. 20 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto20-28. 36 records from Ecsenius caeruliventris and E. shirleyae, two new species of blenniid fishes from Indonesia, and new distribution records for other species of Ecsenius.. 14473 records from Entomology at ZMUC, Natural History Musem of Denmark. 1015 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Macuira. 12065 records from Tromsø Museum, Bryophytes. 164 records from Plasm bearing foraminifera counts from M35/1_MSN1064. 159 records from Phytoplankton abundance at station CD47_0606C#7. 8 records from Phytoplankton abundance at station Casma_2003-06-24_1, Casma, Peru. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 720 records from (Table 5) Distribution of planktonic foraminifers in ODP Hole 126-793A. 86154 records from Naturalis Biodiversity Center (NL) - Coleoptera. 4 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Frank Haubrich. 4 records from Range table from planktonic foraminifers in ODP Hole 178-1099A. 20755 records from pins. 582 records from Bioblitz 2013 Copenhagen Denmark. 1 records from Oppiella signata, eine neue Art der Familie Oppiidae aus dem Osterzgebirge (Acari, Oribatei). 126 records from Total foraminifera counts of multinet PO231/3_MSN1336. 184 records from Abundance of calcareous dinoflagellates of sediment core GeoB3603-2. 3 records from Taxonomy of European Damaeidae (Acari: Oribatida) II. Porobelba weigmanni n. sp. (Oribatida, Damaeidae), from East Slovakia, with comments on other known species of the genus. 16 records from Inventarios de Aves de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 216 records from (Table A2) Stratigraphic distribution of major planktic foraminifer species of ODP Hole 198-1210A. 11 records from A new species of Hemigrammus Gill, 1858 (Characiformes: Characidae) from Rio Caura, Venezuela.. 53 records from Alter Lagerplatz und Gartenteich (Dortmund/Hörde). 49 records from Dörnberg. 82 records from Plasm bearing foraminifera counts from M35/1_MSN1050. 56 records from Total foraminifera counts of multinet M21/4_MSN720. 39 records from Sedimentological investigation on core V25-56. 4 records from Microzooplankton abundance and biomass at station NBP97-08-16-3. 1811 records from Western Palaearctic Ectoedemia (Zimmermannia) Hering and Ectoedemia Busck s. str. (Lepidoptera: Nepticulidae): five new species and new data on distribution, hostplants and recognition. 177 records from BIRDRACE Die Kielbris. 6 records from Ostracoda abundance of Hole 13-134. 4 records from Distribution of Quinqueloculina sp. in sediment core 12930-084. 201 records from (Table 2) Relative abundances of calcareous nannofossils in ODP Hole 120-748A. 78 records from Mammals (GNHM-MM). 20 records from (Table 2) Stratigraphic occurrence of selected diatom species from DSDP Hole 12-112. 844 records from (Table 2) Relative abundance of 13 species of planktonic foraminifers of sediment core GIK17938-2. 192425 records from Bryophytes of Ireland. 1 records from Arthropoden aus südostalpinen Höhlen.. 14 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB04 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 1 records from On the Chilopoda from Turkey. 520 records from Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1150 records from RSPB - Great Yellow Bumblebee sightings data in the UK, 1990 onwards (RSPB, BBCT, HBRG).. 69 records from Entdeckertour am Muldestausee 1/05. 77 records from Distribution of planktonic foraminifera of sediment core SH1972_1. 213 records from Coccoliths in sediment core PS1113-1. 4 records from Nannofossil abundance of Hole 8-75. 2208 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 162 records from Bases de datos de Tanaidaceos (Crustacea: Peracarida) del Mar Caribe mexicano. 1011 records from Biodiversidad fitoplanctónica de cenotes: Patrones espaciales y temporales. 4012 records from Distribution of dinoflagellate cysts in Eocene-Oligocene sediments of ODP Hole 151-913B. 1833 records from DSMZ Fungi. 9625 records from Epiphytic Lichens of G. Lettau at the Botanical Museum Berlin-Dahlem. 501 records from Planktic foraminifera assemblage in sediment core GIK17045-3. 6 records from Pseudogramma xanthum, a new replacement name for a serranid fish from the subtropical South Pacific Ocean with description of the species.. 28038 records from HAS - Herbário Alarich Rudolf Holger Schultz. 151010 records from Marie-Victorin Herbarium (MT). 19 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 120 records from Total foraminifera counts of multinet PO247/2_MSN1387. 1 records from Microzooplankton abundance and biomass at station TT050_25-4. 15 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2177-3. 2 records from Nannofossil abundance of Hole 74-526. 105 records from (Table 1) Occurrence of Early Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 7 records from Distribution of planktic foraminifera of sediment core GIK23342-6 at stadium 5.5. 62 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/553-11. 11 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 4 records from Trap data WR2, 1648 m. 9 records from A new species of Pseudobagrus (Teleostei: Siluriformes: Bagridae) from southern China.. 2109 records from Planktonic foraminiferal abundances, and sea surface and export production reconstructions of sediment core SU92-03. 3189 records from Propuesta para la realización de 37 fichas biológicas de las especies de herpetofauna incluidas en la NOM-059 presentes en la Península de Yucatán. 813 records from Estudio etnobotánico de las malezas útiles presentes en diferentes agroecosistemas en el municipio de Santa María Tecomavaca, Valle de Tehuacán-Cuicatlán, México. 34 records from (Table 6) Temporal variations of relative abundance of dead cells (in detritus, conglomerates and associated with Probocsia alata) of total number of living and dead cells of Emiliania huxleyi at Stations AH-2001-B3 and AH-2001-B3A. 40 records from Range table from planktonic foraminifers in ODP Hole 172-1063A. 441 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 4 records from A new and presumably extinct species of Ptychochromoides (Teleostei: Perciformes: Cichlidae) from central Madagascar.. 321 records from John Muir Trust - Plants and Bryophytes recorded on Schiehallion 25-30 June 2000. 7032 records from EAN - Herbário Jaime Coelho de Moraes. 62283 records from PRECIS (KwaZulu-Natal Herbarium). 269 records from BIRDRACE speedbirder. 127 records from BIRDRACE Southernmost Lakers. 438 records from (Table 3) Distribution of calcareous nannofossils from selected samples of ODP Hole 107-653A. 20 records from (Table 6) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-683B. 2820 records from (Figure 6) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-628A. 14 records from R. Curry Collection. 355 records from Tag der Artenvielfalt. 3413 records from Planktic foraminifera abundance of Hole 23-219. 71 records from Foraminifera abundance of Hole 24-238. 777 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 17720 records from Collection Polychaeta SMF. 5148 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 1168 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 2356 records from Naturalis National Natural History Museum (NL) – Aves_Types. 251744 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 24 records from 10) SST, IRD and benthic foraminiferal d18O data from the Norwegian Sea core MD95-2010: revised chronology for the Last Interglacial (period 134-110 ka). 134 records from Birdrace-Team_Havelland-Havelland. 4 records from Sächsische Schweiz (Wehlener Gebiet). 234 records from Wiesen-Wälder-Wasser um Dansenberg, Biosphärenreservat Pfälzerwald. 2 records from Planktic foraminifera counts of multinet PS2616-5. 2 records from Smear slide analysis of sediment core GeoB7427-2. 418 records from Fossil (GNHM-FO). 1808 records from Ant'Phipoda Database (New records). 3734 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 508 records from Planktic foraminifera abundance of Hole 23-222. 40 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 174-1072A. 18970 records from Cowan Tetrapod Collection - Birds. 367 records from Clyde River Foundation - Twaite Shad (Alosa fallax) distribution for Scotland, historical to present. 68 records from Late Pleistocene planktonic foraminifera of Hole 302-M0004C (Addendum 1). 108 records from (Table 7) Planktonic foraminifera species in bottom sediments of Core ML5_348, North Atlantic. 67 records from Birdrace-Guckers_Offenbach-Offenbach. 1 records from Karpfenteich, Klasse 6d. 753 records from Dinoflagellates (organic) in surface sediments of the South Atlantic. 10 records from Concentration of siliceous microplankton in surface sediments, size fraction 20-40 µm. 1336 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 52359 records from Iziko. 243 records from (Table 1) Oligocene benthic foraminifers abundance in ODP Hole 124-767B. 4 records from Description of lithologic section units of IODP Hole 325-M0034A. 24286 records from Ross A. Layberry Observations. 228 records from MNA (Section of Genoa) and NIWA Invertebrate Collection - Ross Sea Tanaidacea. 76124 records from Lichen field notes, Oslo (O). 336 records from (Table T1) Calcareous nannofossil abundance estimates of ODP Hole 210-1276A.. 81 records from Birdrace-Die_Ornithomaten-Herford. 16 records from Phytoplankton abundance at station Sechin_2003-10-03_2, Casma, Peru. 68 records from (Table 3) Macro- and meiofaunal species abundance in box core samples from the North Pacific Ocean. 92 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 84 records from BIRDRACE Vogelscheuchen. 1666 records from Occurrence of planktic foraminifera in Pliocene to Holocene sediments of DSDP Hole 81-552A in the North Atlantic (Appendix 2). 456 records from Øvre Heimdalsvatn, Radiocaesium (Cs-137) monitored annually in brown trout (Salmo trutta). 26 records from Nannofossil abundance of Hole 37-332A. 13884 records from (Figure 3) Range chart of dinocysts of ODP Hole 104-643A. 6188 records from (Figure 1) Range chart of planktonic foraminiferal species at ODP Hole 107-654A. 874 records from Flora acuática de Querétaro. 245 records from Echuya Survey 2012. 1086 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC17-98. 45 records from Occurrence of mammalia relicts at site Erdhöhle. 101 records from (Table S1d) Measured tomographic parameters for Oridorsalis umbonatus during ETM-2 for ODP Holes 208-1263C and 208-1262A. 13382 records from Herbarium specimens, Harmas J.H. Fabre (FABR - Sérignan-du-Comtat) of the Muséum national d'Histoire naturelle (MNHN - Paris). 6081 records from UNR Herpetology. 1 records from Miriapodi di alcune grotte della Campania. 52 records from Isotope tracer experiment: meiofauna counts. 1243 records from Crustacea ZMK. 115 records from Plasm bearing foraminifera counts of multinet M21/1_MSN614. 113 records from Total foraminifera counts of multinet M21/2_MSN627. 2 records from Nannofossil abundance of Hole 66-489A. 9 records from "Ach, du dicke Eiche", Wald an der Oste-Grundschule Heeslingen. 16 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT008_5-CTD42. 34 records from Two new species of Pseudecheneis, rheophilic catfishes (Teleostei: Sisoridae) from Nepal.. 13 records from (Table 14) Distribution of Pleistocene to late Pliocene nannofossils in ODP Hole 108-668A. 9 records from Microplankton abundance at bottle station SEPT-1999-K8. 71 records from Occurrence of mammalia relicts at site Teufelsbrücke. 535 records from Benthic foraminifera abundance of Hole 73-522. 24 records from Range table from benthic foraminifers in ODP Hole 192-1185B. 709 records from Range table from benthic foraminifers in ODP Hole 139-857A. 2353 records from Relative abunances of benthic foraminifera in Late Oligocene to Miocene sediments of ODP Hole 121-757B from the southeastern Indian Ocean (Appendix Table 1). 14 records from Collection Pantopoda SMF. 2 records from Pollen analysis of sediment profile KR0 from Kreutzsee. 6328 records from Naturalis National Natural History Museum (NL) – Indo-Pacific Plio-Pleistocene fossils. 1391 records from Lichen herbarium, NMBU. 372 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 33 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, 30-63 µm fraction. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 78 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1a. 2419291 records from British Bryological Society - Bryophyte data for Great Britain from the British Bryological Society held by BRC. 21 records from Nannofossil abundance of Hole 19-192. 500 records from Plant (HBBG-PL). 11 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-097BX. 337 records from Zooplankton of the Eastern South Pacific, Universidad de Guayaquil, Ecuador (OBIS South America, SOUTH PACIFIC NODE). 9858 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 13 records from Planktic foraminifera abundance of Hole 60-460A. 1 records from Fourmis récoltées à Madagascar, par le Dr. Conrad Keller.. 1 records from Zetes longiusculus. 455 records from (Table T2) Calcareous nannofossil abundance across the Oligocene/Miocene boundary of ODP Hole 189-1168A sediments. 1 records from Nothrus biciliatus. 140 records from Dinoflagellate cysts counted on two fractions of surface sediment samples from stations A-9 to A-39. 2 records from Microzooplankton abundance and biomass at station TT050_11-4. 25 records from Phytoplankton abundance at station Sechin_2003-11-25_2, Casma, Peru. 14 records from Phytoplankton abundance at station Sechin_2003-12-28_1, Casma, Peru. 4 records from Nannofossil abundance of Hole 31-293. 9858 records from Planktic foraminifera distribution on sediment core GIK17957-2. 3 records from Planktic foraminifera abundance of Hole 17-166. 14 records from Range table from planktonic foraminifers in ODP Hole 143-865B. 15575 records from (Appendix A) Planktonic foraminifer abundance and ranges of ODP Hole 165-999A sediments. 269 records from Range table from planktonic foraminifers in ODP Hole 182-1126C. 603 records from Polish Arctic Marine Programme (EurOBIS). 42 records from (Table 2) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-543. 107 records from RSPB - Crested tit wintering survey in the UK, 1992-1995 (RSPB). 2963 records from MfN - Diptera Collection. 2458 records from Colección de Ictiología. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 88018 records from NINA Vanndata øvrige arter. 1 records from Oribates angulatus. 98 records from Colección Nacional de Heliconias. 20 records from Hübsche Kröten, Wetterfrösche und andere Froschnaturen. 287 records from BIRDRACE Pody und Co. 13 records from Content of coarse fraction and G. menardii in sediment corev V25-49. 2300 records from Botanical Society of the British Isles - Demonstration set of data downloaded from the BSBI threatened plant database. 3 records from Sarcodine counts and carbon biomass at station TT011_4-CTD46. 1380 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 126-790. 48 records from Pollen counts of sediment core GeoB9503-5. 199 records from La fauna de Melolonthidae, Cerambycidae y Elateridae (Insecta: Coleoptera) de la reserva de la biósfera El Triunfo, Chiapas. 60 records from (Table 2) Quantitative parameters of the Emiliania huxleyi population at the section along 70 m isobath carried out on 26 and 27 August 2001. 25793 records from NCOS1959_Crustacea (OBIS China). 1322 records from Planktic foraminifera abundance of Hole 29-284. 767 records from Phytoplankton abundance in surface water in February 1998, Paita, Peru. 157 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera of surface sediment off Morocco (Table 6). 27290 records from Bird Monitoring Data. 399 records from CECT Spanish Type Culture Collection(Fungi). 21 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100260. 90 records from Planktic foraminifera abundance of Hole 24-233A. 1 records from Siphonaptera fossil - SMNG. 1 records from Arthropoden aus südostalpinen Höhlen.. 28 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 470 records from Spiders_of_French_Guiana. 14605 records from DMNS Mammal Collection (Arctos). 43 records from Assemblage of living benthic foraminifera in sediment core CD145_55808#3, 63-150 µm. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-01-10. 4 records from Herpetology Collection. 13 records from Benthic macrofauna abundance of sediment core 13200-081. 84 records from Seawater carbonate chemistry and processes during experiments with phytoplankton Emiliania huxleyi (strain Bergen 2005), 2010. 32356 records from Actualización de la base de datos del Atlas Mastozoológico de México. 441 records from Planktic foraminifera distribution of sediment core 75KS76. 187 records from Taxonomic revision of the Pachycondyla apicalis species complex (Hymenoptera: Formicidae).. 360 records from Küstenschutzwald. 1 records from Streuobstwiese Alt Necheln. 291 records from Benthic foraminifera counts of sediment core GIK17730-4. 159 records from Plasm bearing foraminifera counts of multinet M21/1_MSN606. 785 records from Faunal distribution of the most important planktic foraminiferal species in the investigated surface sediment samples from the Chilean continental slope between 23°S and 44°S. 14 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/323-1. 42 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Florian Werner. 8 records from Zoobenthos in surface sediments in the Yalta Bay. 609 records from Herbier L. Mulon (BOUM). 230 records from (Table 1) Relative abundance of benthic foraminifera in ODP Hole 112-679D. 25 records from Heavy minerals of sediment core PL94-08. 750 records from (Table 20) Benthic foraminifera in early Miocene sediments of DSDP Hole 90-594. 7881 records from Algaterra Types. 1612 records from Plant Specimens of Wakayama Prefectural Museum of Natural History. 546 records from 20 Jahre Naturschutzgebiet Dreienberg. 196 records from Range table from planktonic foraminifers in ODP Hole 162-986D. 181724 records from ArtenFinder. 113482 records from KUBI Ornithology Collection. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 10 records from Ecsenius niue, new species of blenniid fish, and new distribution records for other species in the Opsifrontalis species group.. 129 records from Total foraminifera counts of multinet M12/3_MSN561. 122 records from Total foraminifera counts of multinet M21/2_MSN651. 98 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1381. 17 records from Taxonomy and distribution of the ant Cataglyphis setipes (Hymenoptera: Formicidae). 56 records from Range table from planktonic foraminifers in ODP Hole 167-1010C. 22 records from Coleoptera identified from the Hornchurch Marshes site, Dagenham, London. 215 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 322 records from Nannofossil abundance of Hole 15-147. 52 records from Meiofauna abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas ?. 37 records from Planktic foraminifera abundance of Hole 29-279. 63 records from Range table from benthic foraminifers in ODP Hole 172-1062B. 5316 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 19 records from (Table S2) Calcareous nannoplankton morphometric analyses performed of DSDP Hole 62-463 samples. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1 records from Microplankton counts and carbon biomass at station TT011_3-CTD33. 2 records from Nannofossil abundance of Hole 1-4. 3 records from Analyses of the recent components of sediment core PS1010-1. 1322 records from Targeting a portion of central European spider diversity for permanent preservation. 191 records from Herpetofauna laguna El Tinije. 145 records from Ostracoda abundance in DSDP Leg 87 holes. 1584 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 2794 records from Diversidad bentónica de la laguna Celestún, Yucatán. 2524 records from (Table 13) Ranges of benthic foraminifers through the early to middle Miocene in ODP Hole 115-715A. 16 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/012-5. 52 records from Nannofossil abundance in sediment core PS1297-4. 67 records from (Table 2) Distribution of ostracodes in ODP Hole 107-650A. 1323 records from Estación Experimental de Zonas Áridas (CSIC), Almería: EEZA-Ungulados. 935041 records from NatureServe Network Species Occurrence Data. 35 records from Akita Prefectural Museum＋Reptiles Specimens of Akita Prefectural Museum. 31 records from Planktic foraminifera assemblage in sediment core GIK17732-1. 2504 records from Collections data on ecology of bottom animal of the Southern ocean. 420 records from (Table 4) Relative abundances of planktonic foraminifera in Pliocene sediments of ODP Site 161-975 in the Mediterranean Sea. 160 records from Schulgelände Schule auf der Aue, Münster. 16 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 37 records from Range table from benthic foraminifers in ODP Hole 182-1128D. 1578995 records from Inventaire National du Patrimoine Naturel : Flore Franco-Belge. 465 records from Fish catch from 1996/97 Voyage 2 WASTE (WOCE Antarctic Southern Transect Expedition). 131 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Hole 182-1127B. 16 records from A review of the gobiid genus Akko (Teleostei: Gobiidae) with description of a new species.. 13909 records from Albany Museum. 12509 records from The Bat Conservation Trust - Hibernation Survey. 82 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 8 records from Aktion des Romain-Rolland-Gymnasiums. 7 records from Nannofossil abundance of Hole 49-409. 7 records from Solifugae Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 5 records from Ventichthys biospeedoi n. gen. et sp. (Teleostei, Ophidiidae) from a hydrothermal vent in the South East Pacific.. 44 records from "Schlechteberg" Ebersbach/Sa.. 64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 75 records from Foraminifera species abundances from tow TT007_8-MOC15. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_6-CTD67. 15902 records from Field Museum of Natural History (Botany) - Historical Photographs of Type Specimens from Berlin (B). 4 records from Nannofossil abundance of Hole 29-284A. 15 records from Meiofauna abundance in sediment core 54301-016. 138 records from (Table 2a) Species composition of planktonic foraminiferas in bottom sediments from Core AK6-434-1. 5552 records from MAR - Herbário do Maranhão. 66 records from Occurrence of mammalia relicts at site Malerfels_I. 98 records from Occurrence of mammalia relicts at site Felsställe. 116772 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 51499 records from NRM-Fishes. 3637 records from Lepidoptera collection of NW Europe. 39 records from A review of the Malagasy Pachypanchax (Teleostei: Cyprinodontiformes, Aplocheilidae), with descriptions of four new species.. 9396 records from RSPB - White-tailed eagle reintroduction in Scotland - Sightings data (RSPB/SNH). 144765 records from Invertebrates Collection of the Swedish Museum of Natural History. 11 records from Vögel im Garten Kindergarten Zaisertshofen. 146 records from Total foraminifera counts from multinet M31/2_MSN891. 40 records from (Supplementary Table 2) Estimates of bottom-water oxygenation at site GeoB11185-1. 3347 records from Mammal and Fish speciemens of Kumamoto City Museum. 39650 records from (Table T1) Miocene planktonic foraminiferal stratigraphy of ODP Hole 184-1148A. 1 records from Damaeus torvus. 4778 records from SO-Polylist. 1371 records from (Appendix 2-7) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 59-451 in the western Pacific Ocean. 8 records from Diatom abundance measured on water bottle samples at station PS58/091-4. 32466 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2005) (AfrOBIS). 48 records from Planktic foraminifera abundance of Hole 6-47. 135656 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, 2004-2009. 632 records from Dinoflagellate abundance in sediment core JM06-WP-04-MCB. 25727 records from Irish National Badger Sett Database. 5 records from (Table T9) Calcareous nannofossil stratigraphy of ODP Hole 198-1211C. 16282 records from Atlas der Raubfliegen Deutschlands - database. 100429 records from ICN - Herbário do Instituto de Ciências Naturais. 36459 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 54 records from Planktic foraminifera abundance of Hole 15-146. 4 records from Pachycondyla nigrita and related species in Southeast Asia.. 1735 records from The Flora of County Clare. 139 records from Revision of the myrmicine ants of the Adelomyrmex genus-group (Hymenoptera: Formicidae).. 2 records from Ein Beitrag zur Landtierwelt von Korfu. Chilopoda. 16 records from Assemblage of living benthic foraminifera in sediment core CD145_55818#4, >150 µm. 69 records from Faunal assemblage of sediment core GS7603-7. 65 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211670-7. 933 records from (Table T3) Planktonic foraminifera abundance of ODP Site 170-1041 sediments. 88 records from Microfossil abundance of Hole 16-157. 156948 records from NBI. 10 records from schlittschuhweiher. 3666 records from (Table 5) Stratigraphic ranges of selected Oligocene to earliest Miocene planktonic foraminifers in ODP Hole 115-709A. 1035 records from Estudio de la diversidad florística en la región de la Chinantla, Sierra Norte de Oaxaca. 342 records from (Table 1) Dinoflagellate cysts and acritarchs in upper Pliocene and Pleistocene sediments from ODP Hole 151-911A. 1184 records from iziko South African Museum - Marine Mammal Collection (AfrOBIS). 73821 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1986) (AfrOBIS). 81 records from Range table from planktonic foraminifers in ODP Hole 180-1109D. 3 records from (Table 5) Organic matter contents and paleoproductivities at DSDP Site 75-532. 68 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 51 records from Packer Collection / Xenochilicola bees, Chile. 54 records from Three new species of Gastromyzon (Teleostei: Balitoridae) from southern Sarawak.. 120 records from Birdrace-The_early-Birds-Minden/Lübbecke. 7 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 40 records from Nannofossil abundance of Hole 21-205. 78 records from Nannofossil abundance of Hole 27-262. 143811 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations (OBIS Canada). 6 records from Planktic foraminifera abundance of Hole 23-226. 37 records from Range table from benthic foraminifers in ODP Hole 146-891A. 850 records from RSPB - Crossbills, Distribution survey in Great Britain, 1995-2005 (RSPB). 154 records from Dermaptera in the icipe collection. 1 records from Scutellista caerulea (Fonscolombe, 1832) (Hymenoptera: Pteromalidae), new to New Zealand for the second time!. 79186 records from All Ireland Non-Marine Molluscan Database. 302 records from Kohlstattbrunnental. 91 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 542 records from Planktic foraminifera abundance of Hole 18-175. 384 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru. 358 records from (Appendix 3, Table 4) Relative abundances of benthic foraminifera in Late Quaternary sediments of core BMR96GC21 in the southeast Indian Ocean. 3550 records from Herbarium specimens of Institut Scientifique Mohamed V university (RAB). 184 records from (Table 2b) Biomass of macrobenthos species in samples from Cruise AMK54 stations in the Novaya Zemlya Trough. 7 records from Additions to the myxobiota of the Åland Islands. 327284 records from Fungi (S). 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 960 records from (Table 4) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Site 167-1013 sediments. 113 records from Plasm bearing foraminifera counts from M35/1_MSN1062. 166 records from Plasm bearing foraminifera counts of multinet M21/1_MSN610. 13 records from Planktic foraminifera counts of multinet PS31/002. 3 records from Sarcodine counts and carbon biomass at station TT007_7-CTD76. 7 records from Microzooplankton abundance and biomass at station NBP97-08-29-1. 68 records from Microzooplankton abundance measured on water bottle samples at station PS58/088-4. 10 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2159-3. 55 records from Seeufer ehem. BUGA-Gelände. 153299 records from Insekten Sachsen. 11 records from Benthic macrofauna abundance of sediment core 13200-017. 134 records from Planktic foraminifera counts of sediment core V19-202. 1803 records from Vertebrate specimens of Jyväskylä University Museum. 171 records from Hormigas de hojarasca asociadas a fragmentos de bosque y cafetales de la zona cafetera de Cundinamarca. 26835 records from Herbario Pontificia Universidad Javeriana. 1894 records from Aves Playeras y Otras Aves Asociadas a Arrozales en los Departamentos de Casanare y Meta en 2009 - 2010. 2330 records from Seaweed (Plantae) Collection of the Seto Marine Biological Laboratory, Kyoto University. 111 records from Birdrace-Uhulogen-Lippe. 11 records from Umgebung Jugendherberge Clausthal, Klasse 8d. 134 records from Total foraminifera counts from M35/1_MSN1046. 193 records from Total foraminifera counts of multinet M21/3_MSN663. 46 records from Liether Park (LMS), 5a. 1649 records from MfN - Trace fossils. 1154 records from Collection Plecoptera - SMF. 205599 records from CABI Bioscience Fungus Collection. 69009 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1989) (AfrOBIS). 568 records from Planktic foraminifera assemblage in sediment core SU92-21. 28 records from (Appendix A3) Paragloborotalia morphometric and coiling data from Oligocene sediments of ODP Site 199-1218 in the equatorial Pacific. 20 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB06 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 1092 records from Range table from planktonic foraminifers in ODP Hole 155-936A. 3952 records from Range table from benthic foraminifers in ODP Hole 159-962D. 333 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Charadriidae. 13898 records from TEPB - Herbário Graziela Barroso. 51 records from University of Amsterdam (NL) - Páramo Vegetation Research, Bordoncillo - Nariño, Colombia. 765 records from Colección de peces marinos del mar argentino y aguas adyacentes del INIDEP. 122 records from VFD-BW, Linzgau: Pferdeweiden Neuweiler Hof. 142 records from (Appendix C) Average nannofossil abundances in mid-Pliocene sediments from the equatorial Atlantic. 3 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Frederike Proewe. 7 records from Analyses of the recent components of sediment core PS1402-2. 2310 records from (Table 15A) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-593. 745 records from Gunma Museum of Natural History, Mammal Specimen. 968 records from (Table T17) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones P14-P18. 58 records from A revision the Australian species of the ant genus Myrmecina (Hymenoptera: Formicidae).. 124 records from Total foraminifera counts of multinet M21/1_MSN620. 1309 records from Mongolian Plant (MMNH-PL). 296 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE233. 4500 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene of ODP Hole 105-645E (Table 1). 390 records from (Table 3) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the upper part of the Cismon core. 1099940 records from DOF 2001-2006. 3 records from Nouvelles fourmis de Madagascar.. 764 records from BioGIS - Fish - INPA database. 1376 records from (Appendix B) Abundance of dinoflagellates in sediment core MD01-2378. 1584 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 112-681. 91 records from (Table 1) Distribution of Lower Cretaceous calcareous nannofossils in ODP Hole 123-765C. 55 records from (Table 2c) Species compositioon of planktonic foraminiferas in bottom sediments from Core ML1_66. 407 records from Myriapoda - SMF. 929 records from Flora acuática vascular de las regiones hidrológicas R66 (Lagos Cráter del Nevado de Toluca) y R67 (Río Amacuzac-Lagunas de Zempoala), México. 3 records from Meiofaunal abundance, biomass, taxon richness and indices of nematode diversity of samples from the Santa Maria di Leuca Bank (southern Adriatic margin). 1395 records from Birds - Wild Birds (KIDR-BI). 677 records from Insect colletion. 2320 records from Planktic foraminifera assemblage of sediment core ELT49.018-PC. 66 records from Planktic foraminifera assemblage in sediment core GeoB1113-4. 1073 records from Relative abundance of planktic foraminifera in sediment core RC17-69. 459 records from NSG Karwendel. 677 records from Meiofauna abundance of central Mediterranean Sea mud volcano sediments. 1851 records from (Figure 2) Foraminifera in lower to middle Albian sediments of DSDP Hole 80-549. 129 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 2312 records from Mycological collection of the National Museum. 36 records from Selz (Ingelheim am Rhein). 6 records from Fließgewässeruntersuchung am Haselbach. 4 records from Nannofossil abundance of Hole 9-81. 9322 records from (Figure 3) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548A. 13842 records from BCCM/LMG - Laboratory of Microbiology Gent Bacteria Collection. 1614 records from New Brunswick Museum Collection. 2 records from Schistura papulifera, a new species of cave loach from Meghalaya, India (Teleostei: Balitoridae).. 380 records from Artenvielfalt der Nordsee - Helgoland. 6 records from (Table 1d) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the Late Neopleistocene - Holocene activity phase of the Keli Volcanic Highland. 178 records from RSPB - Corn bunting surveys on the Western Isles. 433 records from Caracterización de las coberturas vegetales en el gradiente altitudinal Páramo-Bosque en los complejos de Páramo de Guerrero y Altiplano Cundi-boyacense. 77605 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 1641 records from NCSM PaleoBotany Collection. 58 records from Schulhof der Astrid-Lindgren-Schule und Umgebung (Elmshorn). 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-14, >125 µm fraction. 34 records from Numbers and dry weights of meiobenthos taxa in surface sediments at Fladen Ground station 1, North Sea (Table 6). 140 records from Distribution of planktonic foraminifera of sediment core SH1972_17. 2 records from Nannofossil abundance of Hole 3-17A. 8 records from Nannofossil abundance of Hole 49-412A. 48 records from Nannofossil abundance in sediment core PS1314-4. 18 records from (Table 1.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Polarstern cruise ANT-XXIII/7. 12 records from Nannofossil abundance of Hole 74-528A. 9256 records from Hemiptera collection (EH) of the Muséum national d'Histoire naturelle (MNHN - Paris). 5920 records from Alterra (NL) - Microarthropods inventories by Henk Siepel on various locations. 33070 records from CSIRO Ichthyology provider for OZCAM. 1905 records from BioGIS - Reptiles - INPA database. 7380 records from University of Ghent - Zoology Museum - Invertebratacollectie. 153 records from Distribution of planktic foraminifera (125-250 µm) of sediment core PS1909-2. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-18-5. 31 records from Pollen profile V and Ausfluss at Krumbach, Germany. 6 records from Relationships of the New World cichlid genus Hypsophrys Agassiz 1859 (Teleostei: Cichlidae), with diagnoses for the genus and its species.. 154124 records from Arizona State University Lichen Collection. 53 records from Planktic foraminifera assemblage in sediment core GIK23041-1. 718 records from Zukünftiges NSG Höftland/Bockholmwik. 275 records from Wald und Wiese am Buchwald. 29362 records from Highland Biological Recording Group - HBRG Vertebrates (not Badger) Dataset. 24 records from Range table from planktonic foraminifers in ODP Hole 170-1039A. 494248 records from British Lichen Society - BLS Mapping Scheme dataset, 1750-2009. 663 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Lacewings and Allies (BNHS) - 1942-2009. 2 records from Lubbockichthys myersi, a new species of dottyback fish from Guam (Pseudochromidae: Pseudoplesiopinae).. 64 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 137 records from Planktic foraminifera counts of sediment core V28-25. 918 records from (Fig. 4) Assemblage of benthic foraminifera in sediment core GeoB6725-1. 79 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1375. 1 records from Microplankton counts and carbon biomass at station TT008_6-CTD64. 16 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/313-1. 9 records from Abundance of radiolaria at station UT99-24-1. 448 records from Geometry of coccolith Gephyrocapsa in sediment core GIK23062-1. 16 records from Nannofossil abundance of Hole 24-235. 73 records from Macrofauna abundance in surface sediment sampled during cruise DI222/2. 316 records from (Table 2) Distribution of planktonic foraminiferal tests in sediments from Core ML7_475. 56081 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Herbario COFC). Facultad de Ciencias. Universidad de Córdoba. 408 records from Visual Plants (144.41.33.158) - Private collection of Rainer Bussmann. 45 records from Range table from planktonic foraminifers in ODP Hole 182-1130C. 23099 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 4132 records from (Table 2) Calcareous nannofossil abundance in ODP Hole 164-994C sediments. 1769 records from Distribution of benthic foraminifera in DSDP Hole 24-238 in the Central Indian Ocean (Appendix A). 20 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, >125 µm fraction. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD85. 14 records from Microzooplankton abundance and biomass at station NBP97-03-11-1. 30 records from Microzooplankton abundance measured on water bottle samples at station PS65/553-3. 17 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/321-1. 2 records from Wie viel Natur gibt es im Park?. 12 records from Microplankton abundance at bottle station SEPT-1999-K4. 4318 records from Diptera Collection of Museum and Institute of Zoology PAS. 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 1 records from Opamyrma hungvuong, a new genus and species of ant related to Apomyrma (Hymenoptera: Formicidae: Amblyoponinae). 33 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, turbidite sequence 3. 152 records from Planktic foraminifera counts at CTD station M39/4_402CTD-55. 180 records from Phytoplankton abundance off Guañape islands in Juli 2003, Peru. 44 records from Flora und Fauna in unserer Kita. 500808 records from Neptune Deep-Sea Microfossil Occurrence Database. 29 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 17 records from Meiofauna abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 258 records from BIRDRACE Raumpatrouille Oriolus. 7774 records from BioGIS - Hamaarag. 17520 records from Arthropod collection, Tromsø Museum. 2784 records from (Figure 3) Distribution of benthic foraminifers in the Albian of DSDP Hole 71-511. 2760 records from RMT Trawl catch from the 1995/96 V4 BROKE voyage. 3477 records from Aves laguna El Tinije. 1256 records from Foraminifera abundance of Hole 64-481. 1042 records from Planktic foraminifera abundance of Hole 37-333. 7 records from Range table from planktonic foraminifers in ODP Hole 169-1038H. 90 records from Range table from benthic foraminifers in ODP Hole 146-889B. 424 records from Taxonomic Revision of the Ant-Acacias (Fabaceae, Mimosoideae, Acacia, Series Gummiferae) of the New World. 12768 records from (Table 4) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-872C. 1 records from Damaeus auritus. 459 records from Colección de Entomología - Coleoptera - Chrysomeloidea. 28 records from (Table 2) Oligocene to Pliocene nannofossil range chart for ODP Hole 134-828A. 123845 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 27 records from Hybridization in Umbridae in the Hudson River, New York, with Designation of Neotypes for Umbra limi and Umbra pygmaea.. 28 records from Smear slide analysis on sediment core GeoB4217-5. 3772 records from Fish (KIWE-PI). 389 records from (Table 2) Distribution of planktonic foraminifera in DSDP Hole core 90-594. 51 records from Planktic foraminifera assemblage in sediment core GIK23066-2. 3 records from Analyses of the recent components in the sand fraction of sediment core PS1403-1. 510 records from Planktic foraminifera counts of sediment core V20-242. 32 records from (Table 4) Carbonate and washed residue weight percentages in ODP Hole 121-758B. 20 records from (Table 2) Abundance and biomass of the main microplankton biota components in the Murmansk coastal pelagic zone in March 1998. 96489 records from Colección Ornitológica del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 14 records from Occurrence of mammalia relicts at site Crumstadt 1. 15 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 11 records from Occurrence of mammalia relicts at site Rotselaar. 33 records from Description of two new species of Avicularia Lamarck 1818 and redescription of Avicularia diversipes (C. L. Koch 1842) (Araneae, Theraphosidae, Aviculariinae) - three possibly threatened Brazilian species. 17 records from (Table A) Fauna associated with Bathymodiolus azoricus mussel beds within the Menez Gwen hydrothermal field, Mid-Atlantic Ridge. 101 records from BIRDRACE nabu-rhein-main.de. 56 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 30-63 µm fraction. 238 records from Abundance of planktic foraminifera at CTD station PS55/081-1. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-23-2. 958 records from (Table 6) Planktonic foraminifera in ODP Holes 139-856A and 139-857A. 279 records from Koleopterologen am Bausenberg. 2 records from Nannofossil abundance of Hole 14-144A. 5 records from Pollen record of a sediment profile from Lake Teletskoye. 2178 records from Flora exsiccata Bavarica. 214 records from Benthos abundance in surface sediment sampled during cruise ANT-V/1. 122 records from A contribution to the study of the Lower Volga center of scarab beetle diversity in Russia: checklist of the tribe Aphodiini (Coleoptera, Scarabaeidae) of Dosang environs. 19 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 6 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cariamidae. 19 records from Three new species of Microbrotula (Teleostei: Ophidiiformes: Bythitidae) from the Indo-West Pacific.. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 13616 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 1 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 161 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 53 records from BIRDRACE Taubenhaucher. 331 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_93MC. 22 records from Abundance of Globorotalia menardii of sediment core GeoB2822-2. 138 records from Total foraminifera counts of multinet M11/1_MSN520. 12 records from Abundance of radiolaria at station LV28-44-1. 177 records from Donauinsel des BN bei Entau. 4 records from MfN - Fossil vertebrates II. 101 records from Nannofossil abundance of Hole 64-476. 2 records from Nannofossil abundance of Hole 74-525A. 219 records from (Table 2) Stratigraphic distribution of planktonic foraminifera from the middle Miocene to upper Miocene in ODP Hole 134-832B. 13 records from Benthic macrofauna abundance of sediment core 13200-008. 214 records from Planktic foraminifera counts of sediment core V27-86. 18 records from Smear slide analysis on sediment core GeoB4206-1. 39 records from Stausee Weiditz. 383 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 22 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/043-2. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_5-CTD56. 5 records from Nannofossil abundance of Hole 3-22. 19 records from (Table 2) Range chart of calcareous nannofossils from Maud Rise sediment cores. 1638 records from (Table 1) Relative abundances of benthonic foraminifera in ODP Site 116-717. 1185 records from (Appendix A) Foraminifera and stable carbon and oxygen isotope record of ODP Site 105-646. 1116 records from CUBA:Herbario del Jardín de los Helechos, Centro Oriental de Ecosistemas y Biodiversidad, Santiago de Cuba: BSC-Pteridophyta. 146624 records from Plants of Papua New Guinea. 185 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 289 records from Odonata del Museo de Entomología de la Universidad del Valle. 14882 records from NCSM Mammals Collection. 68304 records from IICT Herbário LISC. 1695 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 103 records from Wasserwerkspark (Chemnitz). 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 58 records from VFD-H. Heidenrod: Mähweide im Wasserschutzgebiet. 46 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 63-125 µm. 76 records from Plasm bearing foraminifera counts of multinet M36/2_MSN1107. 379 records from WNMU Fish Collection (Arctos). 3440 records from Actualización de la base de datos del proyecto H278 Apoidea (Hymenoptera) del Valle de Zapotitlán de las Salinas, Puebla. 950 records from (Table 9) Distribution of planktonic foraminifera in the early Pliocene to Holocene section of ODP Hole 149-900A. 80846 records from Colección de Lepidópteros del Museo de Zoología 'Alfonso L. Herrera', México (MZFC, UNAM). 3304 records from Planktic foraminifera abundance of Hole 41-369A. 151 records from Planktic foraminifera abundance of Hole 11-104. 1851 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Pisces_Types. 43 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1017. 2222 records from UWYMV Bird Collection (Arctos). 819 records from (Table T4) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P7-P8. 5263 records from Colección Herpetológica (anfibios) de la Universidad Industrial de Santander. 1453 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales de afloramiento rocoso del Parque Nacional Natural El Tuparro. 2913345 records from Especímenes INBio. 61 records from Wälder im Hainbachtal. 24 records from Counts (2) of calcareous dinocysts along profile Stevns-Klint. 349178 records from AMNH Herpetology Collections. 642 records from Planktic foraminifera counts of sediment core V22-196. 83 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Cumacea.. 372 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 197 records from (Table 7) Relative abundance of benthic foraminifera in ODP Hole 112-683A. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station SEPTEMBER-1995-D4. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 260934 records from DINA. 1373 records from Finnish Entomological Database: Araneae. 4567 records from Herbarium WRSL, Main Collection. 8326 records from Derbyshire Biological Records Centre - Derbyshire Invasive Vascular Plants (INNS) 1900 - 2011. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 7 records from Sarcodine counts and carbon biomass at station TT008_5-PMOC6. 279 records from Late Cretaceous and Cainozoic bathyal Ostracoda of DSDP Site 62-463 in the Central Pacific (Fig. 3). 17369 records from MfN - Auchenorrhyncha Collection. 316 records from Moss species from Heard Island, 1987 and 2000. 37 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100800. 85 records from Range table from benthic foraminifers in ODP Hole 154-929B. 2193 records from Hemiptera (Homoptera) collection of National Museum of Nature and Science. 12 records from Spider hosts (Arachnida, Araneae) and wasp parasitoids (Insecta, Hymenoptera, Ichneumonidae, Ephialtini) matched using DNA barcodes. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 54 records from Biotope im Schulumfeld. 215 records from (Table 2) Distribution of sinsitral and dextral fohsellids in middle Miocene sediments of ODP Hole 130-806B from the Ontong Java Plateau, Pacific Ocean. 1431 records from (Table 10) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-712A. 329 records from Fig. 11: Benthic foraminifera assemblage of sediment core MD97-2131. 33 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Ramphastidae. 36 records from Abundance of algae in the Aral Sea. 97 records from Range table from planktonic foraminifers in ODP Hole 182-1133B. 290 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 11 records from Oberservation of birds at station PS14/145 along 49° West. 13230 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Conidae. 7360 records from (Figure 6) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-550. 1445 records from (Table T4) Planktonic foraminiferal stratigraphy of ODP Hole 173-1069A sediments. 65 records from (Table 4) Pleistocene nannofossil range chart for ODP Hole 134-827A. 235 records from Total foraminifera counts from multinet M31/3_MSN905. 27 records from (Table F3) Occurrence of some well known benthonic foraminiferal species in samples from DSDP Site 6-50. 5 records from Nannofossil abundance of Hole 6-53A. 304 records from Planktic foraminifera counts of sediment core V29-173. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 176 records from INSECT COLLECTION. 79 records from Occurrence of mammalia relicts at site Rislisberghöhle. 234 records from Occurrence of mammalia relicts at site Pestera Cioarei. 56 records from Nanoplankton abundance at station GeoB2021-3. 46 records from A first integrative study of the identity and origins of the British Dwarf Pill Millipede populations, Trachysphaera cf. lobata (Diplopoda, Glomerida, Glomeridae). 1 records from Deux especes nouvelles pour la science du genre Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). - Two new species for the science in the genus Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). 2498 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1168A sediments. 380 records from (Table 4) Benthic foraminiferal genera in DSDP Core 95-612-16 and 95-612-17. 1 records from Nothrus convexus. 1 records from Nothrus palliatus. 1275 records from (Table T6) Planktonic foraminifera stratigraphy of ODP Hole 198-1209, Zones P12-P18. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 227 records from Total foraminifera counts from multinet M31/3_MSN916. 38998 records from Countryside Council for Wales - 1996 - 2005 CCW Marine Intertidal Phase 1 species dataset. 5817 records from SMNS Palaeontological collection - Amber. 6 records from Nannofossil abundance of Hole 7-63. 4 records from Nannofossil abundance of Hole 77-540. 823 records from Planktic foraminifera counts of sediment core V17-165. 227 records from (Table 6) Chemical composition of basalts from the Mid-Atlantic Ridge in the Doldrums Fault Zone. 11903 records from The Myxomycetes Collection at the V. L. Komarov Botanical Institute, St. Petersburg. 1654 records from (Appendix A5) Relative abundances of planktonic foraminifera of sediment core GeoB1711-4. 166 records from Außenfeuerstelle Königsbol (Hartheim/Meßstetten). 763 records from Bisons Collection. 19 records from Scottish Wildlife Trust - Small Cow-wheat distributions for Scotland 1999 to 2005. 71 records from RSPB - Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010.. 44 records from (Table F3) Occurrence of some well known benthonic foraminiferal species in samples from DSDP Site 6-49. 69 records from Naturpark Kottenforst-Ville 17.6.09. 7 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/091-4. 290 records from Planktic foraminifera counts of sediment core RC11-134. 2084 records from (Appendix 1) Census data of planktic foraminiferal faunas together with estimates of mean annual SST for sediment core R657. 2118 records from Flora de macroalgas del litoral oaxaqueño. 346511 records from ARGOS Satellite Tracking of animals. 29876 records from European Moth Nights. 1296 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC13-229. 6782 records from Zooplankton Abundance Based on Taxa and Life Stages or Size. 621 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 12 records from Microplankton abundance at bottle station SEPT-1999-K9. 23 records from Planktic foraminifera abundance of Hole 29-284A. 324 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru. 49 records from New species of the amphiliid catfish genera Amphilius, Doumea and Phractura and the taxonomy of Paramphilius from West Central Africa (Siluriformes, Amphiliidae).. 106920 records from Naturalis Biodiversity Center (NL) - Lepidoptera. 1174 records from PReCAST Marine Mammal Sightings. 43298 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 174 records from Total foraminifera counts from multinet M31/3_MSN915. 34 records from Foraminifera species abundances from tow TT007_9-MOC18. 9 records from Microzooplankton abundance and biomass at station TT043_6-1. 2864 records from Fossil (WSHN-FO). 13 records from (Table 2f) Nannofossil distribution chart of petroleum well Montara-2. 1794 records from Elephant Seal Sightings, Heard Island. 3318 records from ZOOLOGIA_FCNO_UDEC_CL Foraminiferos_01 (OBIS South America, SOUTH PACIFIC NODE). 1371 records from Planktic foraminifera assemblage in sediment core GIK16773-1. 536 records from Walldorf-Wiesloch: "Natur über den Gleisen". 5 records from Occurrence of mammalia relicts at site Victoria Cave. 1257 records from Faun. 422 records from (Table T1) Planktonic and benthic foraminifer abundance of ODP Hole 183-1138A. 86774 records from Queen Victoria Museum Art Gallery provider for OZCAM. 3275 records from Quantitative Phytoplankton data from Irish lakes (EPA). 121 records from (Table 2) Relative contents of planktonic foraminifera in bottom sediments from the Ashadze-1 Hydrothermal Field. 15 records from Urwald 2 (Bad Waldsee). 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 596 records from Lower Albian l`Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 162 records from Assemblage of living benthic foraminifera in sediment core GeoB4916-4. 133 records from Total foraminifera counts of multinet PO247/2_MSN1379. 45 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1385. 1698 records from MNA Italica 2004_Rauschert dredge_Ross_sea_Mollusca_lgp. 26 records from Phytoplankton abundance in surface water in 1997, Ancon, Peru. 668 records from Phytoplankton abundance during OCEANIA cruise Oceania90. 5 records from The nematoda fauna of sediment samples of Sarso Islands, Red Sea (Table 5). 101 records from Relative abundance of coccosphere-units of sediment core GIK23411-5. 90 records from Quaternary radiolarians from offshore eastern New Zealand, ODP Leg 181, Site 1123, relative abundances. 83 records from Planktic foraminifera abundance of Hole 40-361. 2 records from Benthic foraminifera abundance of Hole 42-376. 16 records from Qualtitative analysis of calcareous dinocysts along profile Stevns-Klint. 2651 records from KTU Pteridophyta. 7 records from (List 1) Fossil record of Mollusca in Schleswig-Holstein, Germany. 2 records from Ueber Chilopoden aus westbalkanischen Hoehlen. 28383 records from Notes from the Mycology Herbarium, Oslo (O). 56302 records from Kathryn Kalmbach Herbarium. 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 119 records from Assemblage of living benthic foraminifera in sediment core GeoB4915-3. 134 records from (Table 1) Benthic foraminiferal distribution at ODP Site 127-794. 2 records from Nannofossil abundance of Hole 58-442B. 630 records from (Figure 3) Distribution chart of benthic foraminifers in ODP Site 126-790. 1536 records from (Table 5) Distribution of planktonic foraminifera in the latest Pliocene to Holocene section of ODP Hole 149-898A. 582 records from (Table 2) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 3-21 from the Rio Grande Rise, South Atlantic Ocean. 226 records from Range table from planktonic foraminifers in ODP Hole 180-1109D. 248 records from Range table from benthic foraminifers in ODP Hole 198-1210A. 52381 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 10061 records from Collembola collection of Arne Fjellberg, Norway. 1425 records from (Fig. 12) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 50-416A in the North Atlantic. 40 records from The identity of Pseudecheneis sulcata (M'Clelland, 1842), with descriptions of two new species of rheophilic catfish (Teleostei: Sisoridae) from Nepal and China.. 40 records from Öhmdwiesen und Göldern (Konstanz). 66 records from Schulhof A.-Lindgren-Schule (Elmshorn). 52 records from Total foraminifera counts of multinet M21/4_MSN713. 4 records from Microzooplankton abundance and biomass at station TT054_17-21. 2464 records from (Table 2) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-698A. 525 records from Range table from planktonic foraminifers in ODP Hole 155-941A. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fregatidae. 261 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 118 records from A Tenebrionid beetle’s dataset (Coleoptera, Tenebrionidae) from Peninsula Valdés (Chubut, Argentina). 169 records from Expedition "Schulgelände". 773 records from Distribution of calcareous foraminifers in sediment core Well 6406/11-1. 378 records from Size of planktic foraminifera at CTD station PS55/077-1. 20114 records from Molluscus specimens of Toyohashi Museum of Natural History. 61234 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1999) (AfrOBIS). 48 records from Planktic foraminifera abundance of Hole 25-241. 93 records from Range table from planktonic foraminifers in ODP Hole 180-1111A. 138 records from Relative abundance of live benthic foraminifera of sediment core M5/2_107MC. 1350 records from ENBI WP 13 Martius C. F. P. von Collection subset (Muenchen). 44 records from (Table 6) Distribution of nannofossils in DSDP Hole 87-583G. 10898 records from Himenópteros Parasíticos en México (UANL). 1 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/565-1. 1473 records from (Appendix 2, Part 1) Distribution of Eocene to Recent benthic foraminifera in ODP Site 113-689. 15 records from Description of lithologic section units of IODP Hole 325-M0032A. 178 records from (Table SD1, Fig. 2) Benthic foraminiferal abundances, preservation states and thickness to diameter ratios from IODP Hole 310-M0005D. 5 records from Two new species of Exallonyx Kieffer (Hymenoptera: Proctotrupidae) from China, with a key to Chinese species.. 240 records from Phytoplankton abundance in surface water in July-August 1996, Pisco, Peru. 311 records from Avena wild species VIR Herbarium. 1 records from Estudio de los frutos y semillas del género Chenopodium en la Argentina. 7551636 records from BirdLife Australia, Birdata. 16324 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 12 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5110-4. 38 records from Phytoplankton abundance at bottle station A1/52. 244 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 15 records from Abundance and composition of meiobenthos in surface sediments at Fladen Ground stations in August 1975, North Sea (Table 4). 1726 records from KTU Pinophyta. 8 records from Nannofossil abundance of Hole 60-458. 15 records from Benthic macrofauna abundance of sediment core 13078-013. 936 records from Bats of Poland. 8220347 records from OEH Atlas of NSW Wildlife. 3378 records from (Appendix 1) Census data of planktic foraminiferal faunas together with estimates of mean annual SST for DSDP Site 90-594. 613 records from Distribution of dinoflagellate cycst at ODP Site 123-765 (Table 1). 1427 records from Evaluación del riesgo de extinción de setenta y tres especies de lagartijas (Sauria) incluidas en la Norma Oficial Mexicana-059-SEMARNAT-2001. 503 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Invertebrados. 9558 records from Modern planktic foraminifera assemblage from surface sediment samples used as reference data set for the reconstruction of Atlantic sea surface temperatures during the last glacial maximum (LGM). 6 records from Sediment properties of core PLG93_BCORE1. 463 records from Range table from planktonic foraminifers in ODP Hole 171-1052E. 218 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 226 records from Molecular and morphological characterisation of new species in the trapdoor spider genus Aname (Araneae: Mygalomorphae: Nemesiidae) from the Pilbara bioregion of Western Australia. 213 records from Poliquetos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMUV). 3219 records from (Figure 6) Planktonic foraminifera distribution in ODP Hole 130-803D. 10175 records from Seil Natural History Group - SNHG Biological Records Dataset. 21663 records from Monitoring data from the federal state Saxony-Anhalt (Germany). 94 records from (Appendix 4) Calcareous nannofossils in ODP Hole 113-689B. 102 records from (Figure 3) Selected benthic foraminifera measurements from sediment core AvH248260-1, Ameralik Fjord, SW Greenland. 18 records from Plasm bearing foraminifera counts from multinet M31/2_MSN889. 20 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station MARCH-1995-D2. 3096 records from Biological Records Centre - Mosquito Recording Scheme. 335 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1170D sediments. 1 records from Celaeno obsoleta. 1087 records from SMNS Palaeontological collection - Tertiary and quaternary invertebrates. 127 records from Birdrace_Schräge_Vögel-Herford. 159 records from Total foraminifera counts of multinet M21/6_MSN789. 56 records from Microzooplankton abundance measured on water bottle samples at station PS65/470-1. 9 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 121 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 94 records from (Table 1) Some abiotic factors and distribution of benthic foraminifers in surface layer of bottom sediments from the littoral zone of the Kunashir Island (Sea of Okhotsk side). 90 records from Late Albian Col de Palluel (SE France, Niveau Breistroffer): results from planktic foraminifera. 6 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR50. 35 records from Range table from planktonic foraminifers in ODP Hole 139-858D. 30409 records from Birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 41 records from Nine genera of Eucnemidae (Coleoptera) new to Peru, with a key to Peruvian genera. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 1 records from Myriopoden von Epirus. 5 records from (Table 1) Late Maastrichtian calcareous nannofossils in DSDP Hole 22-212. 184156 records from The Flora of County Waterford. 17 records from MVZ Herp Observations (Arctos). 22854 records from National Botanic Garden Belgium - Myxomycetes. 1 records from Nothrus bicarinatus. 114 records from BIRDRACE VIE will rock you!. 112 records from Total foraminifera counts of multinet M33/1_MSN1029. 572 records from Planktic foraminifera counts of sediment core V04-32. 3422 records from Distribución y aspectos taxonómicos de los corales pétreos (Anthozoa: Scleractinia) del Pacífico mexicano. 16 records from Description of lithologic section units of IODP Hole 325-M0057A. 1789 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V22-174. 1963 records from Range table from planktonic foraminifers in ODP Hole 157-953C. 406 records from (Table 4) Distribution of foraminifera in the Miocene section of ODP Hole 133-816C. 2265 records from Algae, Specimens, Agder naturmuseum (KMN). 1 records from Hoplophora carinata. 1 records from On the Chilopoda from Turkey. 66 records from Langes Tannen(LMS), Klasse 5d. 46 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/427-6. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-28-3. 7414 records from HJ - Herbario Jataiense Prof. Germano Guarim Neto. 12 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-1. 2 records from Range table from planktonic foraminifers in ODP Hole 139-855D. 29367 records from Geographic distribution of dinoflagellate cysts in surface sediments. 434 records from (Table 4) Benthic foraminiferal community at DSDP Hole 94-609B. 88537 records from PACA-AGP - Herbarium Anchieta. 308 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 2 records from Neue Milbenarten aus Kärnten. 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 26 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraczion 63-125 µm. 26 records from Assemblage of living benthic foraminifera in sediment core CD146_55901#11, >150 µm. 676 records from (Table 4) Distribution of planktonic foraminifera in middle Miocene sediments of DSDP Hole 94-608 in the North Atlantic. 198 records from Total foraminifera counts from M35/1_MSN1047. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN649. 233 records from Distribution of planktic foraminifera (125-250 µm) of sediment core GIK23059-3. 1683 records from (Appendix 2) Distribution of planktonic foraminifera in the last 70 kyr of sediment core MD95-2043 from the western Mediterranean Sea. 777 records from (Table 2) Distribution of benthic foraminifera in ODP Hole 120-748A. 288 records from Gorgonacea specimens of Kuroshio Biological Research Foundation. 40 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 3 records from New synonym of Tipula (Vestiplex) wahlgrenana Alexander, 1968 (Diptera: Tipulidae). 250 records from (Appendix) Relative abundance of some calcareous nannofossils in ODP Hole 119-738C. 17 records from (Table 2h) Nannofossil distribution chart of petroleum well Swan-3St. 497 records from Relative abundance of Quaternary foraminifera of sediment core CRP-1 (App. 1). 1 records from Occurrence of mammalia relicts at site Ejstrup. 268160 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 960 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 140 records from Bunger Hills, 1999/2000 survey - nest sites of snow petrels Pagodroma nivea. 872 records from Colección de Entomología - Hymenoptera - Parasitica. 58031 records from Colección nacional de zoología. 231131 records from MVZ Mammal Collection (Arctos). 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 106 records from NSG Forst Zinna-Jüterbog-Keilberg. 75 records from BIRDRACE Die Kartoffelsäcke. 161 records from Total foraminifera counts of multinet M21/3_MSN671. 150 records from Redescription and generic placement of the spider Cryptachaea gigantipes (Keyserling, 1890) (Araneae: Theridiidae) and notes on related synanthropic species in Australasia. 3 records from Nannofossil abundance of Hole 20-199. 128 records from (Table 5) Distribution of the large, many-chambered Globigerinelloides species in the Calabianca section. 201 records from Mycological collections of the University of Tartu. 15663 records from Collection Herpetologie - SNSD. 14830 records from Parasitic Platyhelminthes Collections. 433 records from (Table S1) Palynology of IODP Hole 302-M0004A. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 777 records from INRA-Versailles Arabidopsis natural variants. 17 records from Schutzgebiet Ochtersum. 3702 records from Vertebrados terrestres del parque nacional Cañón del Sumidero, Chiapas, México. 1167 records from Macroinvertebrate Data BOKU. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station OCTOBER-1994-D4. 31 records from Occurrence of mammalia relicts at site Sainte-Eulalie. 345 records from Range table from nannofossils in ODP Hole 199-1218A. 2324 records from Distribution of living benthic foraminifera in surface sediments of the Norwegian Sea (Table 2). 37 records from A brief review of Triplophysa (Cypriniformes: Balitoridae) species from the Tarim Basin in Xinjiang, China, with description of a new species.. 1069 records from ZFMK Sound Archive. 39 records from Megafauna abundance and biomass from trawl samples obtained during cruise DI231. 23315 records from Gwaii Haanas Invertebrates (OBIS Canada). 2631 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 13746 records from CNIN/Coleoptera. 102 records from Streuobstwiese RSG (Cham). 1355 records from Planktic foraminifera abundance of Hole 18-173. 66 records from Range table from planktonic foraminifers in ODP Hole 151-909A. 255 records from Range table from planktonic foraminifers in ODP Hole 170-1039B. 30 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 3509 records from Entocytheridae (Ostracoda) World Database. 85 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Recurvirostridae. 194 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 1 records from Murcia ephippiata. 39 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 30-63 µm. 51 records from Plasm bearing foraminifera counts from multinet SO119_MSN1285. 2 records from Nannofossil abundance of Hole 10-87. 9 records from (Table 4) Abundance of microalgae in sinking sedimentary material from sediment traps in the northeast Black Sea in September-October 1999. 288 records from Planktic foraminifera abundance of Hole 94-610A. 5 records from Range table from benthic foraminifers in ODP Hole 181-1120C. 56 records from Range table from benthic foraminifers in ODP Hole 181-1121B. 76 records from Live (Rose Bengal stained) benthic foraminifera from surface sediments of the Indian and Pakistan continental margin (Table 1). 6 records from (Table 1) Dinoflagellate cyst zonations at ODP Site 202-1233. 751 records from (Table T5) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1212B, Shatsky Rise, Pacific Ocean. 11591 records from (Table T6) Foraminifer distribution in ODP Hole 188-1167A sediments. 3175 records from Centre for Genetic Resources, the Netherlands, Indigenous Trees and Shrubs. 968 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones Palpha-P3b. 7 records from A new species of Trichomycterus (Siluriformes: Trichomycteridae) from south Brazil and redescription of T. iheringi (Eigenmann).. 126 records from BIRDRACE Die Schwenker-Birder. 394 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1. 49 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC468. 30 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, 63-150 µm. 4 records from Microzooplankton abundance and biomass at station TT054_26-21. 45187 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 31 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto39-47. 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 3381 records from (Table 10B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-588A. 101 records from Birdrace-Herford-Birder-Herford. 180 records from Paul-Gerhardt-Schule Dassel. 671 records from (Appendix B) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene sediments of DSDP Hole 94-610A from the North Atlantic. 97 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1383. 133 records from Abundance of planktic foraminifera at CTD station PS55/018. 21 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD59. 4 records from Nannofossil abundance of Hole 5-32. 182 records from Range table from benthic foraminifers in ODP Hole 182-1128B. 319 records from Dinoflagellate abundance of Hole 38-338. 871 records from Benthic foraminiferal assemblages (dead), surface data. 73 records from Fossil (JNHM-FO). 9 records from Countryside Council for Wales - Sightings & Miscellaneous Data from Countryside Council for Wales (CCW), 2008 onwards. 233 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 2322 records from (Table AT8) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134A. 1 records from On the Chilopoda from Turkey. 34 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 10 records from Phytoplankton abundance at station Sechin_2003-12-17_2, Casma, Peru. 4 records from Stable carbon and oxygen isotope record of Cretaceous planktonic foraminifera from DSDP (Table 1). 482 records from Kühmark bei Wetzlar. 39 records from Ostracoda abundance of Hole 24-238. 6 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-020. 12 records from Chenopodieae. 17876 records from Mycology Herbarium, Trondheim (TRH). 635 records from Distribución, estructura poblacional y variación genética de algunas especies de pinos en peligro de extinción en México. 978 records from Aves de las reservas de la biosfera de Durango: La Michilía y Mapimí. 1309 records from Benthic foraminifera distribution of sediment core BP01-62/06. 83 records from Frau Voss. 4 records from Oribatids from Switzerland IX (Acari: Oribatidae, Mycobatidae 2) (Acarologica Genavensia CI). 92 records from Nottekanal, Klasse 7 - 10. 39 records from Planktic foraminifera abundance of Hole 28-265. 331 records from Range table from planktonic foraminifers in ODP Hole 141-859A. 17966 records from Ornithology Collection. 67 records from Inventario Murciélagos Finca Naranjito, Aracal, Yopal, Casanare. 123006 records from Finnish Entomological Database: Diptera. 2670 records from Colección Teriológica y Ornitológica de la Universidad Tecnológica del Chocó. 51 records from Coccoliths in sediment core PS1295-4. 15918 records from BANDASCA, BAse de DAtos sobre SCArabaeidae. 318 records from Field Study Group of the Dutch Mammal Society (NL) - 2006 - Mammal Survey Galicica National Park, Macedonia. 5583 records from All observations extracted from the Flora of Northumberland and Durham 1831. 734 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Icteridae. 149 records from (Appendix A) Palynofacies raw counts of DSDP Hole 38-338. 274 records from Bernhardsthal. 8 records from Mean values of fractionated primary production and protozoan abundance from the photic layer collected at 50 m depth in Mejillones Bay. 14 records from Occurrence of recent nannoplankton in multi-net sample at M1_NET243, Arabian Sea (Fig. 2). 81 records from (Table 10) Occurrence of benthic foraminifera in ODP Hole 112-688E, Part I. 686 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Friedrich Heincke cruise FHE238. 50939 records from Instituto Pirenaico de Ecología-CSIC: Herbarium JACA. 900 records from Percentages of planktonic foraminifera species in sediment core V30-36. 171 records from Foraminifera abundance of sediment core C1960.201. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station APRIL-1995-D4. 601 records from Dinoflagellate cyst species of sediment core GeoB10732-3. 76 records from Birdrace-Birding_for_Nature-Bonn. 50 records from Artensuche auf den Elbwiesen in Radebeul. 25 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, 63-125 µm fraction. 47 records from Physical properties, geochemistry and ostracoda abundance of sediment core Lz1080. 6887 records from (Figure 13) Distribution of middle Miocene through middle Pleistocene planktonic foraminifera in ODP Hole 132-810C. 1988 records from (Appendix 2) Benthic foraminifera in ODP Hole 160-963A. 9792 records from International Collection of Microorganisms from Plants - New Zealand National Microbial Collection. 7000 records from CCBER Ornithology Collection. 165 records from Total foraminifera counts from multinet M31/3_MSN903. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 105 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1372. 1054 records from Naturhistorisches Museum Mainz, Herbarium Oesau. 6 records from A new genus and five new species of Astieae (Araneae: Salticidae) from Australia, with remarks on distribution. 3 records from Nannofossil abundance of Hole 9-80. 9 records from Nannofossil abundance of Hole 26-255. 12 records from Benthic macrofauna abundance of sediment core 13200-020. 544 records from (Table 1) Stratigraphic distribution of new marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B. 11700 records from (Figure 4) Distribution of benthic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 45 records from Pfrimmersbachtal. 30 records from Occurrence of mammalia relicts at site Stematia. 1 records from Dinoflagellates, pollen and spore abundance of Hole 29-281. 133 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Parulidae. 3341 records from SORO - Herbário do Centro de Ciências e Tecnologias para a Sustentabilidade. 60163 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 117 records from Naturschutzgebiet Kochertgraben. 95 records from BIRDRACE BiBi. 77 records from Plasm bearing foraminifera counts from multinet SO119_MSN1303. 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 324 records from Total foraminifera counts from multinet M32/5_MSN974. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-4. 48 records from Artenerfassung für Jedermann in der Grundschule Kirchboitzen. 109 records from Broadland Environmental Services Limited - Reptile distribution along the River Bure, Broadland (2010). 15 records from Benthic macrofauna abundance of sediment core 13077-093. 18 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE218. 17979 records from Herbario EMMA. Herbario de la Escuela Técnica Superior de Ingenieros de Montes. UPM. 20 records from Occurrence of mammalia relicts at site Niederlehme. 14 records from Two new glyptosternine catfishes (Teleostei: Sisoridae) from Vietnam and China.. 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 26 records from Kinderbauernhof Pinke Panke - Berlin Pankow. 11 records from Microzooplankton abundance and biomass at station TT045_2-1. 6 records from Microzooplankton abundance and biomass at station NBP97-03-09-1. 50 records from NABU-Fläche am Bösselhausener Weg. 234 records from (Table 2) Selected planktonic foraminiferal species and other microfossil data for sedimentcore P69. 326 records from Elasmobranquios del sistema laguna Chantuto-Panzacola y Carretas-Pereyra de la Reserva de la Biósfera La Encrucijada, Chiapas. 2618 records from MAR-ECO (EurOBIS). 617 records from Planktic foraminifera abundance of Hole 23-223. 41 records from Range table from planktonic foraminifers in ODP Hole 180-1110B. 10 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_996. 140 records from (Table 2b) Downcore distribution of live benthic foraminifera of sediment core PS1394-3, Weddell Sea. 161 records from Total foraminifera counts from multinet SO119_MSN1286. 37 records from Plasm bearing foraminifera counts of multinet M27/2_MSN879. 199 records from Palynomorpha in sediment core PM9462-4 from the Laptev Sea. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_2-CTD26. 1597 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Historico_cofc). Facultad de Ciencias. Universidad de Córdoba. 30 records from Range table from planktonic foraminifers in ODP Hole 152-916A. 1 records from Carabodes coriaceus. 94 records from (Table 2) Occurrence of the most abundant nannofossil taxa in middle Cretaceous sediments of ODP Leg 129 sites. 31 records from Description of a new species of Acestridium (Siluriformes: Loricariidae) from Colombia.. 822 records from Isotope tracer experiment: nematode abundance. 25 records from Glyptothorax botius (Hamilton, 1822), a valid species of catfish (Teleostei: Sisoridae) from northeast India, with notes on the identity of G. telchitta (Hamilton, 1822).. 1 records from Oribates picipes. 86 records from Naturerlebnisraum Koppelsberg (Plön). 225 records from Nannofossil abundance of Hole 15-154A. 5 records from Diatom abundance measured on water bottle samples at station PS58/043-2. 666 records from (Table 2) Species composition of agglutinated foraminifers from the abyssal zone of the Pacific Ocean. 899 records from Collection Insecta fossil - SMF. 1796 records from Sea shell specimens database of Mr. Toru Ueda collection, Shizuoka Prefecture Museum of Natural History. 186 records from Schulhof Goethe-Gymnasium (Emmendingen). 62 records from Plasm bearing foraminifera counts of multinet M21/5_MSN728. 15 records from Abundance of Elminius modestus in 2007-03 from an experiment in the Wadden Sea off List, Sylt. 41884 records from Museu Paraense Emilio Goeldi - Ornithology Collection. 141 records from (Table 2) Relative abundance of benthic foraminifera in ODP Hole 112-680B. 324 records from (Appendix B) Planktic foraminiferal assemblages from ODP Holes 113-689B and 113-690B. 2698297 records from Eremaea. 3 records from Analyses of the recent components of sediment core PS1401-2. 39 records from Range table from planktonic foraminifers in ODP Hole 139-856B. 78 records from Range table from planktonic foraminifers in ODP Hole 167-1019C. 2827 records from (Figure 5) Distribution of benthic foraminifers in the upper Eocene, Oligocene, and Quaternary of DSDP Hole 71-511. 255439 records from R. L. McGregor Herbarium Vascular Plants Collection. 3772 records from BOS Arthropod Collection of University of Oviedo (Spain): Opiliones. 1076 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Tuluá, Valle del Cauca. 458 records from Barley French National Collection. 1433 records from (Appendix Table 1) Relative abundances of calcareous nannofossil in the total assemblage of ODP Hole 177-1090D. 783 records from Phytoplankton abundance in surface water during cruise CD61. 128 records from Phytoplankton abundance at station CD47_2805C#5. 66 records from Plasm bearing foraminifera counts of multinet M21/2_MSN642. 5 records from Abundance of radiolaria at station LV28-66-1. 46 records from Nannofossil abundance of Hole 26-254. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 421 records from Planktic foraminifera counts of sediment core RC09-162. 599 records from Planktic foraminifera counts of sediment core V26-41. 364 records from Nekton and plankton counts from neuston net (300 µm) hauls of cruise GAE 1975/76. 626 records from (Table 2) Benthic foraminifera distribution in sediment core ASV11-880-3. 152 records from Sonnentaugemeinschaft. 180 records from Entdeckertour am Muldestausee. 6 records from Planktic foraminifera abundance of Hole 4-24. 1420 records from Planktic foraminifera abundance of Hole 49-407. 35 records from Range table from benthic foraminifers in ODP Hole 181-1124C. 3329 records from The Pisces Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 420 records from Reptilia Collection of Museum and Institute of Zoology PAS. 544 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 1553 records from Colección preservada Jardín Botánico de la Patagonia Extraandina. 46 records from Aktion Wiese und Wegrain Gitzenheide. 47 records from Nannofossil abundance of Hole 86-577. 13 records from Nannofossil abundance of Hole 94-607A. 109 records from Planktic foraminifera abundance of Hole 37-333A. 288 records from Size of planktic foraminifera at CTD station M39/4_402CTD-55. 18 records from Phytoplankton abundance at bottle station GOM3/1. 5644 records from (Appendix 1) Planktonic foraminifera abundances in ODP Site 181-1123. 9494 records from Colección de plantas vasculares del Herbario "Jaime Andrés Rodríguez". LEB. 42 records from Stadtwald Heide. 69 records from Relative abundance of coccolith species in surface sediment samples from the Mid-Atlantic Ridge. 3 records from Nannofossil abundance of Hole 22-212. 580 records from Herpetofauna de la reserva de la biósfera Valle de Tehuacán-Cuicatlán (etapa final). 1394 records from Avifauna de la Isla de Cozumel, Quintana Roo_1. 1620 records from (Figure 5) Distribution of planktonic foraminifers in the Cenozoic sediments of DSDP Hole 71-513. 12717 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 81105 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1998) (AfrOBIS). 97 records from CNIN/Tipos Hymenoptera. 7014 records from (Figure 6) Distribution of planktic foraminifera of ODP Hole 159-958A. 44 records from Leegmoor (Moormerland/Leer). 88 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2214-1. 5 records from Nannofossil abundance of Hole 67-499B. 950 records from (Appendix 2) Late Cretaceous benthic foraminifera of ODP Site 207-1259. 2810 records from REVIZEE Score Sul / Bentos (OBIS South America, BRAZIL). 1 records from (Table 4) Thecosomata in ODP Hole 134-831A. 192 records from (Table AT1) Grain size distribution and stable isotope record of benthic foraminifera of ODP Hole 175-1085A. 229 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS1756-5. 284 records from Botanical collection of the National Museum. 7 records from Nannofossil abundance of Hole 9-78. 19885 records from Natural History Museum Rotterdam (NL) - Chordata collection. 2702 records from (Appendix B) Abundance of benthic foraminifera in sediment cores GIK17964-3 and GIK17964-2. 170 records from (Fig. 3) Relative abundance of Emiliania huxleyi in sediment core MD99-2343. 2115 records from Planktic foraminifera assemblage of sediment core ELT49.021-PC. 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 34 records from Wattenmeer-Safari (Wurster Watt). 414 records from (Table A a) Relative contributions of planktic foraminiferal species in sediment trap series L1/K276-22 at 2000 m water depth. 125 records from Artenbestimmung. 85 records from Range table from planktonic foraminifers in ODP Hole 151-909C. 56685 records from MISS_DC_01MAR2006. 4943 records from Collembola Collection. 49 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 1. 479 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 424 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 16 records from (Table 3) Contusotruncana contusa morphotypes in DSDP Hole 74-527. 2 records from Nannofossil abundance of Hole 1-1. 14590 records from Colección de Mamíferos de la Sierra Volcánica Transversal de México (UAM-I). 48 records from Abundance of phytoplankton in surface water during THALASSA campaign PROSOPE. 761 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Walther Herwig cruise WH220. 40472 records from MEXU/Colección de Briofitas. 21593 records from CNCR/Colección Nacional de Crustaceos. 495 records from Life Science National Tsing Hua University. 42 records from (Appendix 7) Abundance of Neogloboquadrina pachyderma in sediment core MD01-2444. 27 records from (Table 1) Fauna composition of the community of Amphiodia urtica - Nephtys ferruginea in bottom sediments from the central part of the shelf in the California upwelling zone. 150169 records from UWFC Ichthyology Collection. 7 records from (Table 4) Concentrations of PCBs and MeSO2-PCBs in adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 3 records from Planktic foraminifera abundance of Hole 54-424B. 145 records from Planktic foraminifera abundance of Hole 73-524. 33 records from Range table from planktonic foraminifers in ODP Hole 175-1078B. 49133 records from MBML-Herbario - Herbário Mello Leitão. 240 records from Range table from benthic foraminifers in ODP Hole 175-1075A. 463 records from Facultad de Ciencias Exactas y Naturales Universidad de Buenos Aires Coleccion BAFC de Hongos. 662 records from RSPB - Snipe survey of key sites in Britain in 2006 (RSPB and Natural England). 1423 records from Raw counts of dinoflagellate cysts of sediment core DP30PC. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 11 records from Microzooplankton abundance and biomass at station TT043_28-1. 6 records from Microzooplankton abundance and biomass at station NBP97-08-08-1. 4 records from Range table from planktonic foraminifers in ODP Hole 141-862C. 689 records from Range table from planktonic foraminifers in ODP Hole 152-919B. 1 records from The ant genus Pseudaphomomyrmex Wheeler, 1920 a junior synonym of Tapinoma Foerster, 1850.. 51900 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 147 records from Total foraminifera counts of multinet M10/2_MSN295. 10 records from Phytoplankton abundance at station Sechin_2003-08-06_2, Casma, Peru. 129 records from Nannofossil abundance of Hole 29-284. 260 records from Range table from ostracoda in ODP Hole 144-873B. 1 records from Microplankton counts and carbon biomass at station TT007_8-CTD99. 3 records from Akita Prefectural Museum＋Millipedes Specimens of Akita Prefectural Museum. 169278 records from herpetology. 48114 records from MMNH Museum Bird Collection. 2731 records from (Appendix B) Percentages, total flux and fragmentation index of planktic foraminifera for core T89-40, Walvis Ridge (SE Atlantic). 24 records from Range table from planktonic foraminifers in ODP Hole 146-889B. 324 records from Tentaculata collection of National Museum of Nature and Science. 284 records from Collection Mammalogie - ZSRO. 35 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 µm fraction. 33 records from Phytoplankton abundance in surface water in 1998, Ancon, Peru. 2 records from Benthic foraminifera abundance of Hole 42-374. 56 records from Draposa, a new wolf spider genus from South and Southeast Asia (Araneae: Lycosidae). 4 records from Two new species of the genus Chlopsis (Teleostei: Anguilliformes: Chlopsidae) from the Southwestern Pacific.. 1101 records from Colección de Entomología - Orthoptera. 18 records from Two new fish species of the genus Puntius Hamilton (Cyprinidae) from Manipur, India, with notes on P. ticto (Hamilton) and P. stoliczkanus (Day).. 15474 records from Herbarium Erlangense. 5612 records from Marine Biological Association - 2005-Ongoing United Kingdom MarLIN Shore Thing timed search results. 378 records from (Figure 10) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-537. 124 records from (Appendix A1) Cenomanian benthic foraminifera of ODP Hole 207-1258A. 2413 records from Literature based species occurrence data of birds of North-East India. 10 records from Feuchtwiesen Wippertal bei Wippra. 21 records from LBV-Kindergruppen Markt Tussenhausen. 50 records from Total foraminifera counts of multinet M21/5_MSN743. 7 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_230-9. 8 records from Microzooplankton abundance and biomass at station NBP97-03-16-1. 30 records from Phytoplankton abundance in surface water in 2001, Ancon, Peru. 52 records from A new species of Cordyligaster Macquart, reared from caterpillars in Area de Conservacion Guanacaste, northwestern Costa Rica. 18 records from Thirteen new records of ferns from Brazil. 85 records from Birdrace-Die_Paradiesvögel-Herford. 90 records from VFD-RP: Taunus: Kirchenweide Köpplers. 113 records from Tornoer Teich. 40 records from Plasm bearing foraminifera counts of multinet M21/5_MSN733. 27 records from Smear slide analysis on sediment core GeoB4212-2. 51 records from Coccolith counts of multinet M32/5_MSN971. 42 records from Ostracoda abundance of Hole 48-406. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 2072 records from Estación Experimental de Zonas Áridas (CSIC) EEZA - Aves. 9319 records from Itami City Museum of Insects. 1 records from Abundance of benthos infauna at station GIK23038-1. 859 records from Royal Horticultural Society - RHS berberis sawfly (Arge berberidis) monitoring. 150 records from Isotope age and relative abundance of planktonic foraminifera in Core Vulk-34-90, Sea of Okhotsk. 137 records from Planktic foraminifera counts at CTD station PS55/030. 18 records from Phytoplankton abundance at station Rigel_6_2005-04 in April 2005, Chipana, Chile. 470 records from Phytoplankton abundance during Lev Titov cruise LT90/5. 1150 records from Macrozooplankton concentrations estimated from MOCNESS tow samples, Continental Margin Western Antarctic Peninsula, GLOBEC. 150 records from Vegetatively propagated Allium collection. 2500 records from Zooplankton (NSMK-ZP). 125 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 74-525A. 672 records from Colección de Entomología - Curculionidae. 1603 records from Fossil (MNHM-FO). 93 records from (Table 7) Relative abundance of benthic foraminifera in ODP Hole 112-683B. 53 records from Squid collection from 1995/96 V4 BROKE. 2288 records from (Table 2) Distribution of microfossils in the Barrow Group of ODP Site 122-763. 81 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE272. 105 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 6414 records from Colección de referencia de vectores de Leishmania spp (causante de Leshmaniasis cutánea localizada) de la Península de Yucatán y un estudio preliminar en un área endémica de Quintana Roo. ECOSUR_SNIB. 26753 records from Fish collection of the Museum of Nature and Human Activities, Hyogo. 815 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Belgica cruise BG86/1. 11459 records from Herbario de la Universidad de Sevilla, SEV-Historico. 6050 records from CUBA: Herbario de la Academia de Ciencias, La Habana, Cuba: HAC-Pteridophyta. 1221 records from NBM Unionoids. 4 records from Nannofossil abundance of Hole 10-89. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/545-1. 13 records from Benthic macrofauna abundance of sediment core 12930-073. 15 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-2. 1040 records from Foraminifera and ostracods profile from sediment core AV14_K2-3. 539 records from Bay of Puck dataset (EurOBIS). 1513 records from M. Gollop Collection. 1083 records from Percentages of planktonic foraminifera species in sediment core V29-144. 742 records from (Appendix A) Relative abundances of smaller size planktonic foraminifera in latest Maastrichtian sediments of DSDP Hole 74-525A from Walvis Ridge, South Atlantic. 133 records from Naturschutzgebiete um das Christliche-Spalatin-Gymnasium Altenburg. 168 records from Occurrence of mammalia relicts at site Geißenklösterle. 201 records from Planktic foraminifera abundance of Hole 4-31. 4 records from Description of a new species of Labeo (Teleostei: Cyprinidae) from the lower Congo River.. 102 records from Planktic foraminifera abundance of Hole 67-498A. 17400 records from Sam Mitchel Herbarium of Fungi (Denver Botanic Gardens). 206 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 1036 records from Benthic foraminifera distribution of sediment core ASV1200. 235 records from Klutensee. 58 records from Occurrence of mammalia relicts at site Sandalja II. 1047 records from Planktic foraminifera abundance of Hole 21-206. 1 records from Dinoflagellate abundance of Hole 38-343. 33 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Stylops (BNHS) â 1930-1971. 2197 records from Benthic foraminifers of sediment core Svanic90_9004. 73069 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 42507 records from Bird Collection of Museum and Institute of Zoology PAS. 373 records from Otter survey of Ireland 2004 & 2005. 1300 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 476 records from Caracterización Aves IAI-GAICA: Proyecto Cambio Climático. 2275 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 254 records from BIRDRACE Thüringer Becken-Birders. 169 records from Planktic foraminifera counts at CTD station PS55/051. 26 records from Calcareous dinocysts in ODP Hole 80-550B, part 1. 27278 records from UAM Entomology Observations (Arctos). 213 records from 4. Tag der Artenvielfalt, Naturschutzgebiet Hockenheimer Rheinbogen. 40 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200500. 12 records from Occurrence of mammalia relicts at site Dolni Vestonice. 196 records from Foraminifera abundance of Hole 33-317A. 61 records from Range table from benthic foraminifers in ODP Hole 139-857B. 14 records from (Tab. 7) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 43-384, J-Anomaly Ridge, Grand Banks off Nefoundland. 805 records from Relativ abundances of live fauna of benthic foraminifera in surface sediments (Table C2.1). 7920 records from Sinfonevada: Dataset of Floristic diversity in Sierra Nevada forest (SE Spain). 152 records from Nematode abundances in sediments from the Nyegga pockmark area (Norwegian Sea) obtained during the VICKING expedition in 2006. 44 records from Solanum_baretiae. 1 records from On centipedes (Chilopoda) of Albania, 2. 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 2196 records from Total fauna of benthic foraminifera of Hole 44-390A, Blake Nose Plateau, North Atlantic. 5 records from Nannofossil abundance of Hole 29-278A. 63 records from Planktic foraminifera counts of sediment core RC13-154. 18 records from (Table 2) Average major-element composition of glass shards from Toba Tephra Beds in Sumatra, Malaysia, India, and the Indian Ocean. 679 records from Inventaire National du Patrimoine Naturel : Programme national espèces végétales de la Directive Habitat. 3 records from Mammalia (SMNH-MM). 1974 records from Range table from planktonic foraminifers in ODP Hole 160-967E. 116 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Troglodytidae. 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 6 records from Microzooplankton abundance and biomass at station NBP97-08-33-5. 6 records from Two new dolichoderine ant genera from Madagascar: Aptinoma gen. n. and Ravavy gen. n. (Hymenoptera: Formicidae).. 3 records from Re-description of Cultroribula berolina Weigmann, 2006 (Acari, Oribatida, Astegistidae) from Germany with a key for the European species. 458 records from PeECE I - Pelagic Ecosystem CO2 Enrichment Study, Raunefjord, Bergen, Norway, 2001. 87 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2008. 1157 records from ISU Mammals. 10591 records from Planktic foraminifera (%) of sediment core MD97-2151. 111 records from Planktic foraminifera abundance of Hole 9-79A. 1 records from Celaeno rhodomela. 1 records from Hypochthonius pallidulus. 54 records from Herbier de l'Ecole Normale de Bourges (BOUM). 57 records from Heidesee / Halle. 13 records from Distribution of meiobenthos in sediment core M19_238-2 of the northeastern Atlantic (Table 1). 25 records from Ostracoda abundance of Hole 48-404. 39835 records from Lichen herbarium, Trondheim (TRH). 196 records from (Table 2) Distribution of planktonic foraminifera shells of different species in deposits from DSDP Hole 30-289. 5186 records from Distribución conocida y potencial de 48 especies de hongos silvestres comestibles en la región central del país. 565 records from Range table from planktonic foraminifers in ODP Hole 180-1118A. 17450 records from The Scottish Ornithologists' Club - Fife breeding bird tetrad atlas 1991-99. 3082 records from dec2011. 50834 records from Institute of Dendrology PAS, Flora of Sudety Mountains. 102 records from Range table from benthic foraminifers in ODP Hole 139-858A. 164 records from Terrestrial molluscs at the Natural Park of the Serralada Litoral (Barcelona, Spain). 25592 records from Herbarium Amazonense. 5164 records from Inventaire National du Patrimoine Naturel : Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 1 records from A record of Anzygina billi Fletcher & Larivière, 2009 (Hemiptera: Cicadellidae) from New Zealand. 37014 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Reptiles. 220 records from Total foraminifera counts of multinet SO118_MSN1253. 148 records from Total foraminifera counts from multinet SO119_MSN1278. 53 records from Plasm bearing foraminifera counts from M35/1_MSN1058. 147 records from Plasm bearing foraminifera counts of multinet M21/2_MSN656. 22 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5116-2. 44 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 5 records from Trap data GBZ4, 696 m. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_2-CTD1. 308 records from Phytoplankton abundance during G. M. Dannevig cruise GMD91/10. 9 records from Numbers and dry weight of main macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 3). 4 records from Ostracoda abundance of Hole 32-305. 694 records from Gastropoda, scaphopoda and amphineura abundance of surface sediments of the Atlantic continental shelf off Southern Spanish Sahara, West Africa (Table 2). 55 records from "Schule am Inselsee" Güstrow. 2911 records from Distribution of foraminifera of sediment core GeoB1112-4. 9 records from Microzooplankton abundance and biomass at station TT043_11-1. 25 records from Phytoplankton abundance at station Sechin_2003-12-28_2, Casma, Peru. 2224 records from Cambridgeshire & Peterborough Biological Records Centre - Cambridge Lichen group data held by CPBRC.. 319 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the LÃ¬ and Coire Dhorrcail Estate during June 2001.. 864 records from Lower Albian LArboudeysse (Niveau Paquier) range chart in percentages of nannofossils, in SE France. 3 records from Nannofossil abundance of Hole 1-7. 11 records from Nannofossil abundance of Hole 22-218. 9 records from Nannofossil abundance of Hole 11-99A. 484 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 117-726A. 13 records from (Table 3) Distribution of some benthic foraminifera in ODP Hole 108-659A. 240 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part I. 850 records from Riqueza específica y biogeografía de los corales hermatípicos de la sección sur del Golfo de California y las Islas Revillagigedo. 1237 records from Nematode abundance in sediments obtained during RRS Charles Darwin cruise CD179. 65555 records from Mammals Specimens. 230 records from Pilularia Globulifera distribution map in Denmark. 1384 records from Bridel Herbar. 427 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Juergen Homeier. 207 records from (Table 1) Stable isotope ratios of foraminifera in sediment core CH82-20. 6 records from Occurrence of mammalia relicts at site Barova Cave. 1 records from Planktic foraminifera abundance of Hole 54-424A. 272 records from Dinoflagellate abundance of Hole 81-555. 420 records from Phytoplankton abundance in surface water in November 1997, Ilo, Peru. 48 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE218. 21 records from (Table 3) Paleotemperature estimates for ODP Hole 105-646B. 1700 records from Nuevos registros de esponjas del Pacífico mexicano, Mar de Cortés y Archipiélago Revillagigedo. 18 records from Akita Prefectural Museum＋Cnidarians Specimens of Akita Prefectural Museum. 371 records from Planktic foraminifera abundance of Hole 63-470. 27 records from Range table from planktonic foraminifers in ODP Hole 169-1036B. 38 records from Microfossil abundance of Hole 21-206C. 132 records from tab 2. 24972 records from Colección de Herbario. 18 records from RSPB - Black grouse lek survey in Lothian and Borders, 2008 (RSPB). 216 records from (Table 1) Distribution of foraminifera in the Miocene section of ODP Hole 133-815A. 42 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Passeridae. 589 records from (Appendix B) Benthic foraminifera extinction group polpulation of ODP Hole 184-1146A. 915 records from Colección de Coleoptera (Tenebrionidae) del sureste de la Península Ibérica de la Universidad de Granada. 96 records from (Table 2) Neogene benthic foraminiferal community at DSDP Hole 95-613. 1 records from Oribates mollicomus. 112 records from CommunicA Koblenz - Wildkräuterexkursion - Rheinsteig Bornhofer Höhe. 40 records from Streuobstwiesengelände St.Meinrad Gymnasium. 36 records from Ruhrwiesen Arnsberg, Klasse 9 und 10, Fachbereich Biologie. 141 records from Plasm bearing foraminifera counts from multinet SO119_MSN1282. 31 records from Biological data measured on water bottle sampels at station AT_II-119/5_31-7. 71 records from Microzooplankton abundance measured on water bottle samples at station PS58/107-5. 98 records from Distribution of planktonic foraminifera in DSDP Hole 90-594 east of New Zealand. 228 records from Occurrence of mammalia relicts at site Grotte Scladina. 131 records from Siliceous microfossil occurrence, Site 177-1092. 10592 records from Wikander. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 355 records from Culture Collection of Cryophilic Algae. 11729 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Hymenoptera_Bombidae_Types. 148 records from Faunal assemblage of sediment core GS7603-11. 165 records from Total foraminifera counts from multinet M31/3_MSN898. 176 records from Total foraminifera counts of multinet M21/2_MSN656. 134 records from Coleoptera identified from the Bellot Street site, Greenwich, London. 2 records from Nannofossil abundance of Hole 1-4. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/424-3. 1250 records from Colección de Crustáceos Macrobénticos del Golfo de México (ICMyL-DF, UNAM). 21680 records from Osaka Prefectural Minoh Park Insects Museum. 8684 records from Individual Sightings. 66 records from Visual Plants (144.41.33.158) - Private collection of Thorsten Kroemer. 2628 records from GEO Hauptveranstaltung Tirol (Innsbruck). 494 records from Biologische Station im Kreis Wesel. 8 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1994-D4. 17 records from (Table 2) Distribution of Manumiella seelandica in Maastrichtian sediments of the Bass River Section in the southern New Jersey. 16 records from Occurrence of mammalia relicts at site Buchenloch. 114 records from RSPB - Tree sparrow recovery project â summary data, North West England, 2004-2010 (RSPB, NE, Wirral Borough Council, Cumbria Biodiversity Partnership). 779 records from Guadeloupe_Ananas. 1050 records from Relativ abundances of total live fauna of benthic foraminifera in surface sediments (Table C1.1). 50 records from Abundance of birds on the channels of Lena Delta in the nesting period. 661 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 1 records from Arthropoden aus südostalpinen Höhlen.. 100193 records from Mammalogy Collection - Royal Ontario Museum. 27 records from A new species of the gobiid fish Trimma from the Western Pacific and Northern Indian Ocean coral reefs, with a description of its osteology.. 5860 records from Loopkevers Grensmaas - Carabid beetles near the river Meuse in Flanders, Belgium. 66081 records from HUFU - Herbarium Uberlandense. 22 records from Anostomoides passionis, a new fish species from rio Xingu, Brasil (Characiformes: Anostomidae).. 304 records from John Muir Trust - Bryophytes of Glen Nevis Woods 1987-1988. 6 records from (Table 3) Middle Eocene silicoflagellates from DSDP Hole 95-613. 9879 records from Bibliographic records of Angola mammals. 19 records from Distribution of planktic foraminifera of sediment core GIK23059-3 at stadium 5.5. 17 records from Dinoflagellate cysts of sediment core IOW211630-9. 1 records from Microzooplankton abundance and biomass at station TT050_4-7. 656 records from ZFMK Sound Archive. 142 records from MfN - Fossil vertebrates I. 6 records from Nannofossil abundance of Hole 10-91. 128 records from Coccoliths in sediment core PS1535-8. 3800 records from (Figure 7) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-630A. 11 records from (Table 2) Population density and zoobenthos biomass in bottom communities of the Novosibirsk Polynya in September 2008. 72615 records from Marine and Coastal Management - Demersal Surveys (years 1991-1995) (AfrOBIS). 139 records from Planktic foraminifera assemblage in sediment core GIK23071-3. 218 records from Planktic foraminifera assemblage in sediment core GIK16396-1. 113 records from Studies on species of Holarctic Pardosa groups (Araneae, Lycosidae). VII. The Pardosa tesquorum group. 34392 records from Water Beetles of Ireland. 111 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-8. 101 records from Naturgrundstück (Eutin). 58 records from Schulgelände Kranich-Gymnasium (Salzgitter). 21 records from Bach. 5 records from Nannofossil abundance of Hole 67-498A. 11 records from Nannofossil abundance of Hole 11-101. 20672 records from MSB Parasite Collection (Arctos). 2014 records from (Table 10) Distribution of planktonic foraminifers in ODP Hole 112-688A. 2091 records from Estudio florístico de las gramíneas de Zacatecas. 7971 records from Monitoring records of plant species in the Hakone region of Fuji-Hakone-Izu National Park, Japan, 2001-2010. 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 1 records from Arthropoden aus südostalpinen Höhlen.. 3087 records from Herpetile collection, Natural History Museum, University of Oslo. 517 records from Schulzentrum "Parc Hosingen". 64240 records from The Scottish Ornithologists' Club - South East Scotland Tetrad Atlas 1988 - 1994 - non-sensitive breeding species. 10 records from Description of the females of Anapis castilla and Anapisona bordeaux (Araneae, Anapidae).. 5 records from (Table T5) Calcareous nannofossil stratigraphy of ODP Hole 198-1212B. 10 records from Ökowerk Emden. 160 records from Total foraminifera counts of multinet M21/2_MSN658. 9 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE233. 14278 records from (Table 4) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-700B. 147 records from Planktic foraminifera abundance of Hole 22-217. 2486 records from Hawaiian Algal Database. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 73 records from Nannofossil abundance of Hole 73-520. 7 records from Diatom abundance measured on water bottle samples at station PS58/107-5. 365 records from Greater Manchester Ecology Unit - Distribution of Bats in Greater Manchester. 741 records from Biogeographic distribution of Antarctic and sub-Antarctic Mysida. 256 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 138 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV4. 9031 records from AIMS - LTM Nearshore Corals (OBIS Australia). 3420 records from Nova Scotia Museum of Natural History, Halifax, NS, Canada. 5815 records from Coleoptera of Białowieża Forest. 870 records from Percentages of planktonic foraminifera species in sediment core V22-38. 14 records from Occurrence of mammalia relicts at site Joint Mitnor Cave. 15 records from Planktic foraminifera abundance of Hole 17-165. 84 records from Range table from planktonic foraminifers in ODP Hole 141-859B. 14522 records from MVZ Egg and Nest Collection (Arctos). 104 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Motacillidae. 33 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 76 records from (Table T2) Calcareous nannofossil stratigraphy of ODP Hole 198-1214A. 808 records from (Table 2) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 113-690C on Maud Rise, Weddell Sea. 105 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB06 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 33 records from Occurrence of mammalia relicts at site Gamssulzenhöhle. 22 records from Planktic foraminifera abundance of Hole 6-48B. 258 records from Planktic foraminifera abundance of Hole 40-364. 1 records from Range table from planktonic foraminifers in ODP Hole 139-858F. 110 records from Range table from planktonic foraminifers in ODP Hole 144-875C. 20 records from Range table from planktonic foraminifers in ODP Hole 175-1078C. 13 records from Range table from benthic foraminifers in ODP Hole 194-1192A. 60 records from Range table from benthic foraminifers in ODP Hole 139-858C. 356 records from MGC Herbarium of University of Malaga (Spain): MGC-Lichen dataset. 60 records from crocodylus. 17170 records from Herbier Louis-Marie (QFA) - Collection de bryophytes. 70508 records from CU Invertebrate Paleontology. 46664 records from The Scottish Ornithologists' Club - Fife non-breeding bird 5km atlas 1991-99. 18 records from Rita macracanthus, a new riverine catfish (Teleostei: Bagridae) from South Asia.. 28385 records from Plan de vertebrados de la Patagonia. 9526 records from UK Cetacean Strandings Investigation Programme - Stranded cetacean data from Great Britain collected from 01/01/89 through to 31/03/10. 600 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Accipitridae. 761 records from Dorset Environmental Records Centre - Dorset Heath - NBN South West Pilot Project Case Studies. 66 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 94 records from FFH-Gebiet Paartal. 58 records from Plasm bearing foraminifera counts of multinet M12/3_MSN560. 1496 records from Countryside Council for Wales - Stoneworts in Wales. 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 976 records from (Table T2) Planktonic foraminifera abundance of ODP Site 170-1040 sediments. 250 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 9 records from Polyrhachis (Myrma) cyaniventris F. Smith, 1858 (Hymenoptera: Formicidae) and a related new ant species from the Philippines.. 5116 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 73 records from A new handfish, Brachionichthys australis sp. nov. (Lophiiformes: Brachionichthyidae), with a redescription of the critically endangered spotted handfish, B. hirsutus (Lacepede).. 1447 records from Odonata of the Congo River 2010 expedition. 5 records from Feuchtwiese. 140 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 15 records from Plasm bearing foraminifera counts of multinet PO231/3_MSN1330. 4 records from Microzooplankton abundance and biomass at station TT054_7-18. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_8-CTD102. 140 records from Distribution of late Turronian planktonic foraminifers in ODP Hole 114-700B. 37986 records from rmca-albertine-rift-cichlids. 1 records from Microfossil abundance of Hole 42-378. 140 records from Plant Living in Water (KIDR-PL). 680 records from (Table 1) Distribution of larger benthic and planktonic foraminifers in ODP Hole 135-841B. 1 records from Oribates fusifer. 1030627 records from Phanerogamic Botanical Collections (S). 1353 records from Colección de Entomología - Diptera - Ceratopogonidae. 172 records from Leben im Finkensteiner Moor. 174 records from BIRDRACE Bon(n)apartemöwen. 3 records from Sarcodine counts and carbon biomass at station TT011_5-CTD64. 88 records from Dinoflagellate abundance of Hole 28-274. 5549 records from Diplopoda (NSMK-DI). 6 records from Review of the genus Metopheltes Uchida, 1932 (Hymenoptera, Ichneumonidae) with description of a new species from Vietnam. 2476 records from EcoRecord - Bug (Hemiptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 493 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 3. 7 records from Cordylancistrus nephelion (Siluriformes, Loricariidae), a new and endangered species of suckermouth armored catfish from the Tuy River, north-central Venezuela.. 38 records from Plasm bearing foraminifera counts of multinet M21/5_MSN742. 80 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1361. 172 records from Total foraminifera counts of multinet PO247/2_MSN1371. 7 records from Planktic foraminifera counts of multinet M21/5_MSN732. 9 records from Microzooplankton abundance and biomass at station NBP97-03-05-6. 11 records from Distribution of meiobenthos in sediment core M19_232-2 of the northeastern Atlantic (Table 1). 3718 records from Benthos counted on dredged samples during Valdivia cruise VA53. 110 records from Artenvielfalt und Kulturlandschaft. 51 records from (Table 1) Total cyst counts and concentrations of dinocysts and pollen together with environmental parameters. 5918 records from Catálogo y recopilación de datos científicos de los lepidópteros nocturnos de México, pertenecientes a cinco familias. 127 records from (Appendix E) Stable carbon and oxygen isotope composition of Globigerinoides sacculifera of ODP Hole 121-758B. 217 records from Birdrace-Ornis_im_Einsatz-Lahn-Dill-Kreis. 89 records from Total foraminifera counts from multinet SO119_MSN1303. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN734. 8 records from Microzooplankton abundance and biomass at station TT045_29-1. 4286 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 109266 records from Recent Invertebrates Specimens. 845 records from Planktic foraminiferal assemblages of the Paleocene-Eocene Thermal Maximum from ODP Hole 198-1209B, Shatsky Rise, Pacific Ocean. 23048 records from Herpetology Collection. 40 records from Macrofauna biomass in surface sediment sampled during cruise DI226. 836 records from (Figure 4) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-626D. 174 records from Birds (NHCA-BI). 58614 records from Marine and Coastal Management - Demersal Surveys (years 1986-1990) (AfrOBIS). 1017 records from Broadland Environmental Services Limited - Water vole distribution within Broadland (2003-2006): based upon field signs, sightings and trapping data.. 1 records from Abundance of benthos infauna at station GIK23062-2. 13 records from Environment Agency - Environment Agency white-clawed crayfish Survey of the River Lune Catchment 2004. 510 records from (Table S2) Relative abundance of coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 10633 records from Biological Records Centre - Collembola Recording Scheme. 83 records from Spechtwald. 40 records from Flächennaturdenkmal Grubditz. 26946 records from Diveboard - Scuba diving citizen science observations. 32 records from Biological data measured on water bottle sampels at station AT_II-119/5_35-4. 5 records from Microzooplankton abundance and biomass at station TT050_7-9. 29 records from Range table from ostracoda in ODP Hole 151-911A. 857 records from Artenvielfalt am Eich-Gimbsheimer Altrhein. 1 records from Mesozoa - SMF. 54 records from Species occurring in the mytilid and alvinellid communities within the 9°N hydrothermal field at the East Pacific Rise. 1360 records from Contribución a la riqueza ictiofaunística de la Reserva de Ría Lagartos, Yucatán. 9271 records from APIS - Antarctic Pack Ice Seals 1994-1999, plus historical data from the 1980's. 641 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Northwest African upwelling area. 242 records from Schieferbrüche. 30 records from Nannofossil abundance of Hole 94-608. 14 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/048-3. 19 records from Cottus kanawhae, a new cottid fish from the New River System of Virginia and West Virginia.. 103 records from (Table 6b) Calcareous nannofossil distribution on ODP Hole 117-731C. 753 records from Estación Experimental de Zonas Áridas (CSIC) EEZA-Mamif. 436 records from Larval fish at Helgoland Roads in 2005. 1272 records from (Table 2) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-706A. 1010 records from Distribución y algunos aspectos ecológicos de hongos hidnoides estipitados de México. 384824 records from Herbarium, Botanical Museum, University of Oulu, Finland (OULU). 181 records from Marine Biological Association - RISC and ALERT Marine Non-Native Species (Chinese Mitten Crab, Wakame and Carpet Sea Squirt) Records. 140 records from Occurrence of mammalia relicts at site Jägerhaus-Höhle. 44 records from Planktic foraminifera abundance of Hole 19-188. 389 records from Inventaire National du Patrimoine Naturel : CBN Bailleul. 244 records from Range table from benthic foraminifers in ODP Hole 145-887C. 81 records from Revision of the snailfish genus Allocareproctus Pitruk & Fedorov (Teleostei: Liparidae), with descriptions of four new species from the Aleutian Islands.. 596 records from MISE Project Roaringwater Bay Otter Records, 2012-2014. 2 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 31 records from (Table 4) Abundance of under-ice amphipods on flat ice and ice ridges sampled during the 2005 Hidden Ocean expedition. 2994 records from Museu de Ciències Naturals de Barcelona: BGJBB. 559 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Meiofauna. 1534 records from PonTaurus collection. 655171 records from Bugbase, Lepidopterological Society. 10 records from Occurrence of mammalia relicts at site Adler Cave xx. 5 records from Range table from planktonic foraminifers in ODP Hole 171-1049C. 12 records from Phytoplankton abundance in surface water in October 1995, Ilo, Peru. 10 records from Oberservation of birds at station PS14/149 along 49° West. 13583 records from Highland Biological Recording Group - HBRG Fungus, Lichen and Lower Plants Dataset. 1284 records from Collection of Heteroptera. 16 records from (Table V) Distribution of diatoms in samples from Heidemann Valley trench, Antarctica. 2 records from Hornmilben (Oribatida) [pages 323 to 417]. 1 records from A new myrmicine ant genus from Malaysia with uncertain affinities (Hymenoptera: Formicidae).. 442 records from Distribution of planktic foraminifera of sediment trap NB7. 8 records from Abundance of radiolaria at station LV28-29-1. 601 records from LBV 100 - Artenvielfalt am Rothsee. 2 records from Nannofossil abundance of Hole 9-82. 21 records from Meiofauna abundance in sediment core 12930-018. 73 records from Planktic foraminifera counts of sediment core V24-28. 70 records from Korean Aquatic Vascular Plants. 9674 records from Mammal collection of National Museum of Nature and Science. 3015 records from Bird specimens in Gifu Prefectural Museum. 155 records from Bergbaufolgelandschaft am Muldestausee. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station AUGUST-1994-D2. 14219 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 21 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD56. 12 records from Phytoplankton abundance at station Casma_2003-04-14_1, Casma, Peru. 1151 records from Coccolithophores in surface sediments of the Arabian Sea (TAble 1). 9 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/043-2. 1 records from Schneifelkinder erkunden südliche Blumenpracht. 17 records from (Table 3) Nannofossil occurrence in the Albian of ODP Hole 101-635B. 2048 records from (Table 5) Distribution of planktonic foraminifers in ODP Hole 108-659A. 96 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 113-689B. 33944 records from Aranzadi Zientzi Elkartea. 4550 records from University of Alberta Museums, Freshwater Invertebrate Collection. 1359 records from GEO Biodiversity Day. 366 records from Marine fauna survey of the Vestfold Hills and Rauer Island, 1981-82. 323 records from Foraminifera abundance of sediment core IN68-29. 142 records from Birdrace-Alte_Socken-Cuxhaven. 237 records from Planktic foraminifera abundance of Hole 21-207. 4 records from Range table from planktonic foraminifers in ODP Hole 171-1049A. 9 records from Foraminifera abundance of Hole 64-477A. 33 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 174-1071F. 11 records from A new species of Probolomyrmex from Madagascar.. 48 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 234 records from Baggerseen bei Krauchenwies. 138 records from Phytoplankton abundance at station DI182_11863#1. 32 records from Grundschüler erkunden Schulumgebung. 1177 records from Phytoplankton abundance during Mikhail Lomonosov cruise ML47. 569 records from Benthic foraminifera abundance of Hole 84-567A, Part 2. 420 records from Phytoplankton abundance in surface water in January 1996, Ilo, Peru. 19 records from (Table 6) Pleistocene nannofossil range chart for ODP Hole 134-830A. 10 records from Succession of benthic hard-bottom communities abundance at Liliguapi in 2010. 448 records from Biodiverisity Group, Dept. of Environment, Food and Agriculture,Isle of Man Government - Japanese Knotweed Records in the Isle of Man 1991-2008. 232 records from (Table A1) Stratigraphic distribution of calcareous nannofossils of ODP Hole 198-1210A. 4286 records from HUCO - Herbário da Universidade Estadual do Centro-Oeste. 798 records from Biological Records Centre - Irish Otter Dataset. 25128 records from rmca-albertine-rift-butterflies. 271 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 71 records from Birdrace-do_elster_Dortmund. 111 records from BIRDRACE Die Wendehälse. 9 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_209-1. 11 records from Microzooplankton abundance and biomass at station TT045_15-2. 1577 records from (Table 2) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-903A. 83 records from Visual Plants (144.41.33.158) - Private collection of Juergen Homeier. 617 records from (Table 5) Realtive abundance of planktonic foraminifera in sediment core AHF-11343. 80 records from Planktic foraminifera abundance of Hole 49-411A. 612 records from Range table from benthic foraminifers in ODP Hole 149-900A. 63 records from (Fig. 9A) Compiled data of profile L´Arboudeysse, SE France. 149 records from Naturnahes Tal in Siena. 1 records from Nouvelles fourmis de l'Imerina oriental (Moramanga etc.).. 104 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cathartidae. 10 records from Devon Biodiversity Records Centre - Devon giant hogweed data 1997 to 2000. 6 records from MfN - Micropaleontology. 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 16 records from Mollusca Colelction of the Seto Marine Biological Laboratory, Kyoto University. 1 records from Microzooplankton abundance and biomass at station TT050_24-13. 206 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Herpetofauna. 197 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: MAMMALIA_FZ. 601 records from Distribution of planktic foraminifera (112-200 µm) of sediment core M8_057-2 (Table 5). 135 records from Birdrace_Dith_MarshSandpiper-Dithmarschen. 496 records from Range table from benthic foraminifers in ODP Hole 145-887A. 415 records from Dinoflagellate cysts from the Upper Hauterivian (Cretaceous) of a claystone-marlstone succession in the clay-pit Frielingen. 1 records from Oribates gilvipes. 164233 records from ORN. 128 records from (Table 2) Distribution of ebridians and actiniscidians in selected samples from DSDP Hole 90-591. 264 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 1756 records from Relative abundances of middle Pleistocene benthic foraminifera in DSDP Site Site 90-594. 356 records from Amphibia Collection of Museum and Institute of Zoology PAS. 18959 records from Herbarium Specimens of Bonin and Ryukyu Islands. 31 records from Pastinachus solocirostris sp. nov., a new species of Stingray (Elasmobranchii: Myliobatiformes) from the Indo-Malay Archipelago.. 106 records from Rare vascular plant species in North-West of Kostroma region, Russia. 1 records from Nothrus canaliculatus. 74 records from Schulwald Grundschule Brügge. 5 records from Distribution of meiobenthos in sediment core M19_216-2 (2) of the northeastern Atlantic (Table 1). 491 records from Naturschutzgebiet Lüneburger Heide. 28 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of ODP Hole 189-1171D. 336 records from Planktic foraminifera counts of sediment core V19-185. 100125 records from Ohio State University Fish Division (OSUM). 127499 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 56051 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 91 records from CNIN/Tipos Homoptera. 4 records from Pycnogonida collection of National Museum of Nature and Science. 149 records from Biotop Binsenwiesen (Wehrheim/Taunus). 207 records from Geo-Tag der Artenvielfalt Süßen Hornwiesen-Grundschule. 116 records from Occurrence of mammalia relicts at site l´Abri de la Ferrassie. 11 records from Occurrence of mammalia relicts at site Nörre-Lyngby. 685 records from Planktic foraminifera abundance of Hole 4-30. 36432 records from RSPB - Corncrake national surveys - raw data (SCARABBS). 1031 records from (Table 4) Carbon flux, paleoproductivity, relative abundance of foraminifera on sediment core PS2837-5. 1 records from Collection Mammalia fossil SMF. 593 records from Mamíferos voladores laguna El Tinije. 29 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM7. 221 records from (Table T2) Calcareous nannofossil abundance of ODP Hole 171B-1052A sediments. 396314 records from British Lichen Society - BLS Lichen Database: English churchyards. 40 records from Plasm bearing foraminifera counts from M35/1_MSN1057. 2 records from Nannofossil abundance of Hole 1-5A. 380 records from Stable oxygen and carbon isotope ratios of Globigerinoides obliquus of quantitative range chart of the ostracodes in the Pliocene-Pleistocene interval of ODP Hole 107-654A. 218 records from GTI MICROFUNGI OBSERVATION. 44501 records from Canadian National Collection (CNC) of Insects, Arachnids and Nematodes. 332 records from Foraminifera distribution of sediment core SDSE192. 389 records from Planktic foraminifera abundance of Hole 23-228. 850 records from (Table 3) Distribution of benthic foraminifers from ODP Hole 134-828A. 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 2916 records from Orthoptera (Grasshoppers & Crickets) & allied insects of Ireland. 12 records from Schulgelände Erich-Kästner-Schule. 142 records from Total foraminifera counts of multinet M21/2_MSN649. 137 records from Abundance of planktic foraminifera at CTD station PS55/077-1. 10030 records from Free-living marine Nematodes from San Julián bay (Santa Cruz, Argentine), 2009.. 12 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 11 records from Nannofossil abundance of Hole 3-15. 2 records from Nannofossil abundance of Hole 3-18. 60000 records from Birds (NSMK-BI). 11981 records from SMNK Mantid Collection. 104 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Murcielagos. 387 records from Distribución espacio-temporal de las larvas de atunes en el Golfo de Tehuantepec, México. 34 records from Meiofauna abundances in sediments from the Nyegga pockmark area (Norwegian Sea) obtained during the VICKING expedition in 2006. 2255 records from Plant Systematics Laboratory, Ajou University, Korea. 260 records from Range table from planktonic foraminifers in ODP Hole 155-930D. 1088 records from Relativ abundances of total dead fauna of benthic foraminifera in surface sediments (Table C1.2). 281 records from (Table 1) Ostracoda community from DSDP Hole 95-612. 1735 records from Naturalis National Natural History Museum (NL) – Acari_Types. 67371 records from Swedish Board of Fisheries (Fiskeriverket) - Swedish Electrofishing Registry. 63985 records from The First Atlas of Breeding Birds in Britain and Ireland: 1968-1972.. 534 records from (Appendix B) Total cyst counts, and abundances of Selenopemphix undulata sp. nov. in Pacific Ocean surface samples. 2467 records from Coleccion Herpetologica Reptiles LJAMM-CNP. 192 records from (Table 2) Relative abundance of selceted benthic foraminifera taxa of DSDP Hole 93-605. 10007 records from Freshwater fishes of the Western Balkans. 122 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Site 198-1213. 36 records from Range table from benthic foraminifers in ODP Hole 160-967E. 9062 records from Northern Biodiversity Program Coleoptera (2010-2011). 59432 records from JPB - Herbário Lauro Pires Xavier. 49 records from A catalogue of the ants of Paraguay (Hymenoptera: Formicidae).. 97 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 167-1017E sediments. 1371 records from (Table T2) Abundance of dinoflagellates and other palynomorphs in Eocene-Oligocene sediments from ODP Hole 189-1172A. 18 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001I. 632 records from MVZ Hildebrand Collection (Arctos). 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 46 records from 8c. 48 records from Heider Bergsee (Brühl). 112 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 94 records from Total foraminifera counts from M35/1_MSN1074. 133 records from Total foraminifera counts of multinet PO231/3_MSN1334. 340 records from Phytoplankton abundance and species composition in the Gulf of Naples from February to December 1987. 130 records from Abundances of dinoflagellate cysts in sediment trap MST-9 (Appendix 1). 39033 records from SBMNH Vertebrate Zoology. 43 records from Nannofossil abundance of Hole 11-102. 219 records from INERA-Luki reservation herbarium (CABIN project). 26559 records from Taiwan Forestry Research Institute. 25830 records from Colección de Diatomeas del Sur del Golfo de México (ICMyL-DF, UNAM). 27 records from (Table 12) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-688A. 7403 records from Freshwater fishes of Hidalgo state (Mexico) in the MZNA fish collection of the University of Navarra (Spain). 519292 records from Museum Victoria provider for OZCAM. 30926 records from Annelida collection of National Museum of Nature and Science. 33 records from (Table 6) Distribution and abundance of calcareous-nannoplankton species in the Cretaceous sediments of DSDP Hole 62-466. 477 records from (Table 2) Distribution of foraminifera in the Miocene section of ODP Hole 133-816A. 1431 records from (Figure 6) Benthic foraminifera counts of sediment core MD01-2378. 17 records from Dinoflagellate cysts of sediment core IOW211630-9. 1 records from Zetes dorsatus. 2077 records from Vascular plant specimens of Iida City Museum. 4000 records from Fungal Collection of Natural History Museum and Institute, Chiba. 38 records from (Table 19) Nannoplankton distribution in sediment core ANS3-T9. 8 records from Description of lithologic section units of IODP Hole 325-M0049B. 87075 records from Banc de dades de biodiversitat de Catalunya-ArtroCat. 16 records from Phytoplankton abundance during Professor Siedlecki cruise PSied90/1. 24 records from Occurrence of mammalia relicts at site Fuchsloch im Krockstein. 759 records from Planktic foraminifera abundance of Hole 47-398D. 28 records from Planktic foraminifera abundance of Hole 31-301. 73 records from Benthic foraminifera abundance of Hole 80-550. 162 records from (Fig. 2) Abundance of Uvigerina pygmaea in sediment core MD95-2039. 89 records from Dixidae (Diptera) of Ireland. 2782 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Taminango, Nariño. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55916#1, >150 µm. 49 records from Total foraminifera counts of multinet M10/2_MSN238. 197 records from Total foraminifera counts of multinet M21/1_MSN608. 61 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/546-19. 141 records from Phytoplankton abundance at station CD47_3105C#4. 11 records from Phytoplankton abundance at station Sechin_2003-08-06_1, Casma, Peru. 256 records from Planktic foraminifera counts of sediment core V16-20. 14 records from Relative abundance of live benthic foraminifera of sediment core M5/2_91MC. 16632 records from BANDAPHO, BAse de DAtos sobre Aphodiidae. 1001 records from Naturhistorisches Museum Mainz, Botanical Collection. 4288 records from Universitat de Girona: HGI-Cormophyta. 13865 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 1429 records from Morano and Cardoso: AraIb. 298 records from Stausee (Oberdigisheim/Meßstetten). 78 records from Occurrence of mammalia relicts at site Einhornhöhle. 139 records from Range table from planktonic foraminifers in ODP Hole 139-855A. 298 records from Results of palynological analysis of Hole 302-M0002A. 111991 records from Monitoring data from the federal state North Rhine-Westphalia (Germany). 3946 records from EcoRecord - Amphibian records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 101662 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 19 records from Inventario de Aves Pauto J, Yopal, Casanare. 72 records from (Table 1) Distribution of silicoflagellates, actiniscidians, and ebridians in selected samples from ODP Hole 112-682A. 1664 records from Zooplankton of the Eastern South Pacific (OBIS South America, SOUTH PACIFIC NODE). 7926 records from NBM birds. 7 records from Analyses of the recent components of sediment core PS1220-3. 224 records from Bizzenbach-Aue im Bizzenbachtal (Wehrheim/Taunus). 54 records from Range table from planktonic foraminifers in ODP Hole 141-862A. 107 records from (Figure 8) Distribution and character of selected biogenic and lithologic components at DSDP Hole 79-547A. 198044 records from Naturalis Biodiversity Center (NL) - Botany Utrecht. 179 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cuculidae. 44 records from NW-Innenhof Gesamtschule Herten 7.6.2001. 9 records from Microzooplankton abundance and biomass at station TT043_2-1. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD10. 7 records from Phytoplankton abundance at station Casma_2003-02-27_2, Casma, Peru. 14 records from Phytoplankton abundance during Arne Tiselius cruise AT90/1. 9 records from Distribution of hydropolyp species on coral reefs of the Red Sea (Table 5). 7 records from A revision of the Aphaenogaster phalangium complex (Hymenoptera: Formicidae: Myrmicinae).. 76 records from Fish (MNHM-PI). 165 records from (Table 1) Palynomorph concentrations in ODP Hole 105-646B samples. 46 records from Palynomorph data and remarks on dominant tree taxa from IODP Hole 313-M0028A. 62 records from Occurrence of mammalia relicts at site Pestera Livadita. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1422-1. 165 records from Foraminifera abundance of Hole 48-406. 8527 records from HSU Wildlife Birds. 3525 records from Countryside Council for Wales - Important Welsh Bat Roosts Database (BATSITES-WALES). 57218 records from National Biodiversity Data Bank. Observation records, 1900-2014. 21 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rynchopidae. 45 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 125572 records from NINA insect database. 39 records from Südpark (Bochum-Wattenscheid). 8 records from Kleiner Ziergarten Winzingen (Neustadt). 8 records from Krittenhorster Wald (Ostkilver). 1100 records from (Table AT3) Planktonic foraminiferal stratigraphy of ODP Hole 182-1128B. 117 records from Plasm bearing foraminifera counts of multinet M21/1_MSN619. 157 records from Total foraminifera counts of multinet M21/6_MSN787. 164 records from Abundance of planktic foraminifera at CTD station PS55/066. 47 records from Nannofossil abundance of Hole 64-479. 5 records from Nannofossil abundance of Hole 34-320A. 2 records from Nannofossil abundance of Hole 20-199. 856 records from Planktic foraminifera counts of sediment core V27-178. 574077 records from LACM Vertebrate Collection. 7 records from Grundschule Sandheide. 232 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE278. 265 records from AIS Wildtype Populations of Arabidopsis. 5 records from Loricifera - SMF. 247 records from Planktic foraminifera abundance of Hole 63-471. 32 records from A review of the subfamily Acaenitinae Förster, 1869 (Hymenoptera, Ichneumonidae) from Ukrainian Carpathians. 11371 records from Herbario Museo de La Salle Bogotá (MLS). 202 records from Inventario de Aves Buenos Aires, Tauramena, Casanare. 265 records from Luderbusch. 27 records from Naturgarten Vielfalt - Naturlehrgarten Fa. Dehner. 265 records from Geometry of coccolith Gephyrocapsa in sediment core K708-007. 362 records from (Table A.05) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (100-150 µm). 12 records from Abundance of microplankton from bottle APRIL-2000-K1. 14 records from Benthic foraminifera abundance of Hole 96-620. 2318 records from Fundación Miguel Lillo - Colección Ictiológica. 82 records from Countryside Council for Wales - Non-native species records from Countryside Council for Wales (CCW) non-native monitoring research and ad-hoc sightings. 637 records from Countryside Council for Wales - Lamprey Survey Data. 2511 records from (Table T5) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1052E. 1010 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 23227 records from Mollusk data of Molltax, Norway. 9216 records from Inventaire National du Patrimoine Naturel : Crustacés Décapodes de France. 9173 records from Colección de líquenes del Herbario "Jaime Andrés Rodríguez". LEB-Lichen. 2 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2010. 94 records from Total foraminifera counts of multinet PO231/3_MSN1333. 1297 records from Dinoflagellate assemblage in surface sediments of the South Atlantic. 16 records from Dinoflagellate cysts of sediments core IOW211660-6. 11 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_806-1. 177239 records from Inventaire National du Patrimoine Naturel : Données ONEMA sur les poissons et écrevisses d'eau douce.. 13086 records from Collection of Coleoptera. 365 records from Colección Herpetológica de la Patagonia. 1077 records from BioGIS - Fish - HUJ collections. 141 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 1998 records from Institut Botanic de Barcelona, BC-Lichenotheca. 208 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 11 records from Nannofossil abundance of Hole 55-431A. 12 records from Diatom abundance measured on water bottle samples at station PS58/012-5. 74 records from Description of a new Batrochoglanis species (Siluriformes, Pseudopimelodidae) from the rio Paraguai basin, State of Mato Grosso, Brazil.. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB06 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 310 records from Planktic foraminifera counts of sediment core V18-191. 17 records from (Table 3) Stratigraphic distribution of silicoflaggelates, ebridians and actiniscidians in upper Pliocene to Pleistocene sediments of ODP Hole 104-644A. 18894 records from (Table 5) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Site 114-702. 5323 records from Anfibios y reptiles del estado de Nuevo León. 103 records from Invertebrate collections. 168582 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Lepidoptera Observation Records. Pre-2010 for Cumbria. 12963 records from Composition of planktonic foraminifera species from 310 sediments samples during the last glacial maximum. 333 records from Langes Tannen (Uetersen). 30246 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 86 records from Pollen analysis of sediment core GIK16856-2. 150417 records from Natural History Museum, Vienna - Herbarium W. 1868 records from Inventario florístico de la Sierra de San Carlos, Tamps. 606 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Plantas. 6 records from Description of lithologic section units of IODP Hole 325-M0054B. 641 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during LITTORINA cruise LI1986/1. 43905 records from Herbarium of Jyväskylä University Museum. 72316 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1993) (AfrOBIS). 17413 records from Herbarium BSG Vascular Plants. 3 records from Occurrence of mammalia relicts at site Igstadt I. 20 records from Review of the Camponotus aureopilus species-group (Hymenoptera, Formicidae), including a second Camponotus with a metapleural gland.. 177 records from (Table 11) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-589. 35 records from Planktic foraminifera abundance of Hole 67-499A. 121 records from Range table from planktonic foraminifers in ODP Hole 167-1011B. 492 records from Phytoplankton abundance in surface water in October 1997, Chimbote, Peru. 41 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto129-136. 908 records from (Appendix A1) Planktonic foraminifera of ODP Hole 157-951A. 23593 records from New Zealand Biodiversity Recording Network. 10 records from Two new species of eelpouts (Teleostei, Zoarcidae) of the genus Seleniolycus from the Ross Dependency, Antarctica.. 968 records from TTRS Mammals. 14212 records from MOSS - Herbário Dárdano de Andrade Lima. 757 records from Sistemática y biogeografía del género Xenosaurus (Squamata: xenosauridae). 479 records from CBS Bacteria Database. 22 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB03 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 198 records from Microplankton abundance in the euphotic zone of the Aegean Sea in September 1994. 8 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 76 records from Occurrence of mammalia relicts at site Vindija. 220 records from Foraminifera abundance of Hole 57-440. 4196 records from Planktic foraminifera abundance of Hole 37-334. 114 records from Range table from planktonic foraminifers in ODP Hole 171-1052F. 145171 records from DUKE Bryophyte Collection. 12321617 records from Norwegian Species Observation Service. 43 records from Relative abundance of planktic foraminifer Globigerinita uvula in core PS1243. 1 records from Nothrus biurus. 16 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rostratulidae. 5 records from Schulinnenhöfe (Gelsenkirchen). 366 records from Weinberg Reichersdorf. 18 records from Landschaftsschutzgebiet Buchhorst2. 53 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 48 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1197. 13 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 92 records from Abundance of coccosphere-units of site GIK23259. 2346 records from (Fig. 8) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 44-391C in the North Atlantic. 182 records from Relative abundance of live benthic foraminifera of sediment core M5/2_88MC. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 177494 records from Segundo censo de plantas leñosas de una Parcela Permanente de 25 hectáreas, ubicada en la Reserva Natural La Planada (Nariño, Colombia). 1 records from Review of the ant genus Nesomyrmex (Hymenoptera: Formicidae: Myrmicinae) in southern Africa.. 262155 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 16 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 82 records from Plasm bearing foraminifera counts of multinet M27/2_MSN883. 45 records from (Table S2) Age determination of ODP Sites 202-1234 and 202-1235. 6 records from Bayerische Donau - Metten. 6912 records from Bryophyte Collection of Natural History Museum and Institute, Chiba. 47 records from Distribution of calcareous nannofossils in the lower sequence of the CIROS-1 sediment core (Table 2). 103178 records from MfN - Heteroptera Collection. 763 records from Planktic foraminifera assemblage in sediment core GIK17050-1. 1 records from Planktic foraminifera abundance of Hole 8-73. 20 records from Foraminifera abundance of Hole 58-442B. 100 records from Megafauna abundance and biomass in surface sediment during cruise PLG95A. 64 records from (Table 3) Distribution of calcareous nannofossils in Cretaceous sediments recovered in ODP Site 129-801. 352 records from Scottish Natural Heritage - Recovery of the medicinal leech Hirudo medicinalis in Scotland - Phase II. 8 records from Abundance of radiolaria at station UT99-13-2. 1326 records from (Table T9) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones P5-P7. 10358 records from Census of the flora of Benin. 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Aramidae. 105 records from People's Trust for Endangered Species - Noble Chafer: Pre-BAP records prior to 1998. 2 records from Note tassonomiche e faunistiche su Chilopodi della Grecia (Chilopoda). 197 records from Inventaire National du Patrimoine Naturel : CBN Aquitaine-Poitou-Charentes. 270 records from Meiofaunal abundance in sediments obtained during RRS Charles Darwin cruise CD179. 36136 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 2814 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 101 records from Assemblage of total living benthic foraminifera in sediment core SO119_MC501. 3 records from Sarcodine counts and carbon biomass at station TT011_6-CTD71. 753 records from Range table from ostracoda in ODP Hole 144-872C. 14897 records from Rådgivende Biologer. 11 records from Pollen profile Märchenwald C, Harz, Germany. 126 records from (Table 2) Calcareous nannofossil distribution and relative abundance in ODP Hole 114-703A. 88 records from P. W. Lund collection in the National History Museum of Denmark, Copenhagen. 63504 records from UNSM Vertebrate Specimens. 414 records from Naturschutzstation Schmidsfelden. 94 records from Planktic foraminifera abundance of Hole 63-468A. 12 records from Bilder der Natur. 190 records from ENBI-Dataset of GART-GloBIS. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_10-CTD124. 2392 records from (Table 3) Dinocyst ranges in ODP Hole 104-642D. 10 records from (Table 3) Minerals and components of sediments from DSDP Site 94-609_Site, North Atlantic. 63 records from Planktic foraminifera assemblage in sediment core GIK23243-2. 54 records from Occurrence of mammalia relicts at site Rusenschloß. 10 records from Occurrence of mammalia relicts at site Aveley. 1 records from Range table from planktonic foraminifers in ODP Hole 174-1072A. 876 records from Phytoplankton abundance in surface water in July-August 1996, Ilo, Peru. 5042 records from Tracheophyta collection of Biodiversity Center of Japan, Ministry of Environment. 2880 records from Coleoptera, NEF. 31 records from Nationalpark Harz Schul-AG Braunlage. 26 records from Schulteich Heinrich-Mann-Schule. 1294 records from Global Butterfly Information System (GloBIS). 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 31 records from Total foraminifera counts of multinet M10/2_MSN322. 7 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_264-1. 918 records from (Table 4) Occurrence of benthic foraminifera in samples from DSDP Hole 72-518. 50 records from Nannofossi
Keywords: GBIF; biodiversity; species occurrences